Laminated film, polarizing plate and liquid crystal display device
The laminated film, featuring a cellulose acylate and sugar ester substrate with a fumaric acid ester polymer optical functional layer, addresses visibility issues and delamination in liquid crystal display devices, ensuring improved optical performance and interlayer adhesion.
Patent Information
- Application Number
- JP2022528493
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-06-04
- Filing Date
- 2021-04-28
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-04-28
AI Technical Summary
Liquid crystal display devices using retardation films with fumaric acid ester resin layers suffer from visibility issues due to uneven color when viewed from an angle, and delamination occurs in the retardation film.
A laminated film with a substrate composed of cellulose acylate and a sugar ester, combined with an optical functional layer containing a polymer with a high proportion of fumaric acid ester units, is used to achieve good interlayer adhesion and optimal visibility.
The laminated film ensures good visibility in liquid crystal display devices by eliminating color unevenness when viewed from an angle and preventing delamination, thereby enhancing the display's optical performance.
Smart Images

Figure 0007661970000019 
Figure 0007661970000020 
Figure 0007661970000021
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate film, a polarizing plate, and a liquid crystal display device. More specifically, the present invention relates to a laminate film having a fumaric acid ester-based resin layer, which has good interlayer adhesion in a retardation film and can ensure good visibility in a liquid crystal display device using the laminate film, and a polarizing plate and a liquid crystal display device including the laminate film. [Background technology]
[0002] Liquid crystal display devices are widely used in society, from televisions to personal computers and mobile phones, and are used as important devices. In recent years, various optical compensation films have been used to improve the display characteristics of liquid crystal display devices, widening the viewing angle, improving color tone, and improving contrast. Among them, a film made of a fumaric acid ester resin or including a fumaric acid ester resin layer has been proposed as a retardation film having a negative refractive index (see, for example, Patent Document 1).
[0003] However, it has been found that in a liquid crystal display device having a retardation film made of a fumaric acid ester-based resin or having a fumaric acid ester-based resin layer laminated on a substrate on the liquid crystal panel side of a polarizer, there are problems with visibility due to uneven color when the display device is viewed obliquely, there is a difference in color when viewed from the left and right, and delamination occurs in the retardation film having a fumaric acid ester-based resin layer laminated on a substrate. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 5245109 Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention has been made in consideration of the above problems and circumstances, and the problem to be solved is to provide a laminate film having a fumaric acid ester-based resin layer, which has good interlayer adhesion and can ensure good visibility in a liquid crystal display device using the laminate film, and a polarizing plate using the laminate film. Also, the present invention is to provide a liquid crystal display device using the laminate film, which can ensure good visibility. [Means for solving the problem]
[0006] In the process of investigating the causes of the above problems in order to solve the above problems, the present inventors have found that a laminate film having good interlayer adhesion and capable of ensuring good visibility in a liquid crystal display device using the laminate film is obtained by using a combination of a specific cellulose acylate and a sugar ester as a constituent material of a substrate, and by defining a value T (slope of the out-of-plane retardation in the wavelength range of 450 to 650 nm) calculated based on a specific formula from the out-of-plane retardation R650 measured with light having a wavelength of 650 nm and the out-of-plane retardation R450 measured with light having a wavelength of 450 nm in the substrate, within a specific range, and the optical functional layer laminated on the substrate is a polymer substantially composed of polymerization units of fumaric acid ester in which the majority of the ester moiety is isopropyl ester, and by setting the value Rth450 / Rth550 of the out-of-plane retardation Rth450 measured with light having a wavelength of 450 nm and the out-of-plane retardation Rth550 measured with light having a wavelength of 550 nm in the laminate film, thereby achieving the present invention. That is, the above-mentioned problems of the present invention are solved by the following means.
[0007] 1. A laminated film including a substrate and an optically functional layer, the substrate contains cellulose acylate having an acyl group substitution degree in the range of 2.6 to 3.0, and a sugar ester in which hydrogen atoms in 70 to 100% of hydroxyl groups are substituted with acyl groups, a value T calculated based on the out-of-plane retardation R650 measured with light having a wavelength of 650 nm and the out-of-plane retardation R450 measured with light having a wavelength of 450 nm according to the following formula (1) is within a range of 0.040 to 0.055, Formula (1) T=(R650-R450) / (650-450) the optical functional layer contains a polymer containing fumaric acid ester polymerization units in a proportion of 90 mol % or more based on the total polymerization units, and 80 to 100% of the ester moieties of the fumaric acid ester polymerization units are isopropyl ester; The ratio Rth450 / Rth550 of the out-of-plane retardation Rth450 measured with light having a wavelength of 450 nm to the out-of-plane retardation Rth550 measured with light having a wavelength of 550 nm for the laminated film is 1.2 Laminated film in the range of ~1.9.
[0008] 2. The laminate film according to item 1, wherein the laminate film has an out-of-plane retardation Rth550 measured with light having a wavelength of 550 nm within a range of −30 to −15 nm.
[0009] 3. A polarizing plate comprising the laminate film according to item 1 or 2 and a polarizer laminated thereto.
[0010] 4. A liquid crystal display device comprising the polarizing plate according to item 3. Effect of the Invention
[0011] According to the above-mentioned means of the present invention, it is possible to provide a laminate film having a fumaric acid ester-based resin layer, which has good interlayer adhesion and can ensure good visibility in a liquid crystal display device using the laminate film, and a polarizing plate using the laminate film. In addition, it is possible to provide a liquid crystal display device that can ensure good visibility by using the laminate film.
[0012] Although the mechanism by which the effects of the present invention are expressed or the mechanism of action has not been clarified, it is speculated as follows.
[0013] In a liquid crystal display device equipped with a polarizing plate, which is a combination of a retardation film having a fumaric acid ester-based resin layer and a polarizer, on the viewing side of the liquid crystal panel, it was presumed that the light transmitted from the backlight through the polarizer and liquid crystal panel is optically compensated by the retardation film of the polarizing plate, causing internal reflection and interference with surface reflected light, resulting in color unevenness when the liquid crystal display device is viewed from an oblique angle. Therefore, it was thought that color unevenness could be suppressed by controlling the wavelength dispersion of the out-of-plane retardation of the retardation film (hereinafter, the out-of-plane retardation of the retardation film is represented by "Rth")
[0014] Therefore, it was discovered that by combining a fumarate ester-based resin layer and a substrate, the wavelength dispersion of Rth is set so that the ratio Rth450 / Rth550, which is the ratio of the out-of-plane retardation Rth450 measured with light having a wavelength of 450 nm to the out-of-plane retardation Rth550 measured with light having a wavelength of 550 nm, is within the range of 1.1 to 1.9, thereby solving the problem of color unevenness when viewed from an oblique angle.
[0015] In order to adjust the wavelength dispersion of Rth (Rth450 / Rth550) to the above range, the out-of-plane retardation of the substrate combined with the fumaric acid ester resin layer (hereinafter, the out-of-plane retardation of the substrate is represented by "R") was adjusted as follows. Specifically, in a combination of cellulose acylate having an acyl group substitution degree in the range of 2.6 to 3.0 as the constituent material of the substrate and a sugar ester in which hydrogen atoms in 70 to 100% of hydroxyl groups are substituted with acyl groups, the value T calculated based on the above formula (1) from the out-of-plane retardation R650 measured with light having a wavelength of 650 nm and the out-of-plane retardation R450 measured with light having a wavelength of 450 nm was in the range of 0.040 to 0.055.
[0016] In addition, the adhesion between the fumarate ester-based resin layer and the substrate was achieved by setting the ratio of isopropyl ester in the ester portion of the polymerization unit of fumarate ester in the fumarate ester-based resin to 80% or more, and setting the ratio of ester substitution of hydroxyl groups in the sugar ester on the substrate side to 70% or more. It is believed that this is because the above configuration increases the permeability and interaction between the fumarate ester-based resin layer and the substrate. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is a cross-sectional view showing an example of the laminated film of the present invention. [Diagram 2] FIG. 1 is a cross-sectional view showing an example of a polarizing plate of the present invention. [Diagram 3] 1 is a plan view of an example of a liquid crystal display device of the present invention; [Figure 4] 4 is a cross-sectional view of the liquid crystal display device shown in FIG. 3 taken along line XX. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The laminated film of the present invention is a laminated film including a substrate and an optically functional layer, the substrate including a cellulose acylate having an acyl group substitution degree in the range of 2.6 to 3.0 and a sugar ester in which hydrogen atoms in 70 to 100% of hydroxyl groups are substituted with acyl groups, and the value T calculated based on the above formula (1) from the out-of-plane retardation R650 measured with light having a wavelength of 650 nm and the out-of-plane retardation R450 measured with light having a wavelength of 450 nm is in the range of 0.040 to 0.055. The optical functional layer contains a polymer containing fumaric acid ester polymerization units at a ratio of 90 mol % or more to the total polymerization units, 80 to 100% of the ester moieties of the fumaric acid ester polymerization units are isopropyl ester, and the ratio Rth450 / Rth550 of the out-of-plane retardation Rth450 measured with light having a wavelength of 450 nm to the out-of-plane retardation Rth550 measured with light having a wavelength of 550 nm for the laminated film is within the range of 1.1 to 1.9. This feature is a technical feature common to each of the following embodiments.
[0019] As an embodiment of the present invention, from the viewpoint of exerting the effects of the present invention, the laminated film preferably has an out-of-plane retardation Rth550 measured with light having a wavelength of 550 nm within the range of −30 to −15 nm.
[0020] The polarizing plate of the present invention is characterized in that it is formed by laminating the laminate film of the present invention and a polarizer.The liquid crystal display device of the present invention is characterized in that it comprises the polarizing plate of the present invention.
[0021] The present invention, its components, and embodiments for carrying out the present invention will be described in detail below. In this application, the symbol "to" is used to mean that the numerical values before and after the symbol "to" are included as the lower limit and upper limit.
[0022] [Outline of the laminated film of the present invention] The laminate film of the present invention is a laminate film comprising a substrate and an optically functional layer, characterized in that the substrate satisfies the following (1-1) and (1-2), the optically functional layer satisfies the following (2), and the laminate film satisfies the following (3).
[0023] (1-1) The substrate contains cellulose acylate having an acyl group substitution degree in the range of 2.6 to 3.0, and a sugar ester in which hydrogen atoms in 70 to 100% of hydroxy groups are substituted with acyl groups. (1-2) The value T calculated from the out-of-plane retardation R650 measured with light having a wavelength of 650 nm and the out-of-plane retardation R450 measured with light having a wavelength of 450 nm based on the following formula (1) is within the range of 0.040 to 0.055. Formula (1) T=(R650-R450) / (650-450)
[0024] The value T calculated based on the above formula (1) is a value indicating the slope in the wavelength range of 450 to 650 nm in a graph showing the relationship between the measured wavelength and the out-of-plane retardation for the substrate. Hereinafter, the value T calculated based on the above formula (1) from the out-of-plane retardation R650 measured with light having a wavelength of 650 nm and the out-of-plane retardation R450 measured with light having a wavelength of 450 nm is also referred to as the "slope T of the out-of-plane retardation."
[0025] (2) The optical functional layer contains a polymer containing fumaric acid ester polymerized units in a proportion of 90 mol % or more based on the total polymerized units, and 80 to 100% of the ester moieties of the fumaric acid ester polymerized units are isopropyl ester.
[0026] (3) The laminate film has an out-of-plane retardation Rth450 measured with light having a wavelength of 450 nm and an out-of-plane retardation Rth550 measured with light having a wavelength of 550 nm, and the ratio Rth450 / Rth550 is within the range of 1.1 to 1.9.
[0027] The laminated film of the present invention is a laminated film including a substrate and an optically functional layer. The laminated film of the present invention may include layers other than the substrate and the optically functional layer as long as the effects of the present invention are not impaired. FIG. 1 is a cross-sectional view showing an example of the laminated film of the present invention. The laminated film 10 shown in FIG. 1 has an optically functional layer 2 on one main surface of a film-like substrate 1.
[0028] The laminated film 10 of the present invention may have, for example, an adhesive layer between the substrate 1 and the optical functional layer 2. The substrate 1 may be composed of one layer (single layer) or multiple layers, but is preferably a single layer in terms of less display unevenness and the possibility of making the film thinner. The components of the laminated film of the present invention will be described in detail below.
[0029] (base material) The substrate contains a cellulose acylate having an acyl group substitution degree in the range of 2.6 to 3.0 (hereinafter also referred to as "cellulose acylate (A)") and a sugar ester in which hydrogen atoms in 70 to 100% of hydroxyl groups are substituted with acyl groups (hereinafter also referred to as "sugar ester (B)"). The substrate may contain other components other than the cellulose acylate (A) and the sugar ester (B) as necessary within the range that does not impair the effects of the present invention.
[0030] <Cellulose acylate (A)> The substrate contains cellulose acylate (A). The substrate preferably contains cellulose acylate (A) as a main component. Here, the term "main component" means that the content of cellulose acylate (A) in the substrate is 50% by mass or more. The content of cellulose acylate (A) in the substrate is preferably 55% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more. The upper limit of the content of cellulose acylate (A) in the substrate is the remaining amount excluding components other than cellulose acylate (A), and is preferably about 99% by mass, and more preferably 90% by mass.
[0031] Cellulose acylate is a compound in which the hydrogen atoms of the hydroxyl groups of cellulose are replaced by acyl groups. The degree of substitution is a value indicating how many of the three hydroxyl groups per β-glucose residue, which is the structural unit of cellulose, have been replaced on average.
[0032] The acyl group in the cellulose acylate (A) is not particularly limited as long as it is an acyl group represented by RC(=O)-(R is a monovalent hydrocarbon group). For example, the acyl group in the cellulose acylate (A) is preferably an aliphatic hydrocarbon group having 1 to 5 carbon atoms, and is preferably an acetyl group where R is a methyl group, a propionyl group where R is an ethyl group, or a butyryl group where R is a propyl group.
[0033] The acyl group in the cellulose acylate (A) may be one type or two or more types. The acyl group in the cellulose acylate (A) is preferably one type, and the one type is preferably an acetyl group. The substitution degree of the acyl group in the cellulose acylate (A) can be measured in accordance with ASTM-D817-96.
[0034] The acyl substitution degree in the cellulose acylate (A) is 2.6 to 3.0, preferably 2.8 to 3.0. The cellulose acylate is produced, for example, by the method described later. The cellulose acylate (A) may be a cellulose acylate obtained in this manner, which is prepared by mixing two or more cellulose acylates having different acyl substitution degrees, and the degree of substitution may be adjusted to 2.6 to 3.0, preferably 2.8 to 3.0.
[0035] The weight average molecular weight (Mw) of the cellulose acylate (A) is preferably within a range of 80,000 to 300,000, more preferably within a range of 120,000 to 250,000, from the viewpoint of maintaining the mechanical strength of the substrate during stretching. Within the above range, retardation (phase difference) due to stretching during film formation of the substrate can be easily controlled. This makes it easier to satisfy the above condition (1-2) in the substrate.
[0036] The number average molecular weight (Mn) of the cellulose acylate (A) is preferably in the range of 30000 to 150000, since the mechanical strength of the resulting substrate is high. Cellulose acylate having a number average molecular weight of 40000 to 100000 is more preferably used.
[0037] The ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of the cellulose acylate (A) is preferably in the range of 1.4 to 3.0.
[0038] The weight average molecular weight (Mw) and number average molecular weight (Mn) of the cellulose acylate (A) can be measured, for example, by gel permeation chromatography (GPC) under the following measurement conditions.
[0039] Solvent: Methylene chloride Column: Shodex K806, K805, K803G (Showa Denko K.K. three columns connected together) Column temperature: 25℃ Sample concentration: 0.1% by mass Detector: RI Model 504 (GL Sciences) Pump: L6000 (Hitachi, Ltd.) Flow rate: 1.0ml / min Calibration curve: A calibration curve was used using 13 samples of standard polystyrene STK standard polystyrene (manufactured by Tosoh Corporation) with Mw = 1,000,000 to 500. The 13 samples were used at approximately equal intervals.
[0040] The raw cellulose of the cellulose acylate (A) used in the present invention may be wood pulp or cotton linter, and the wood pulp may be softwood or hardwood, but softwood is more preferable. Cotton linter is preferably used from the viewpoint of peelability during film formation. The cellulose acylates made from these may be used alone or in appropriate mixtures.
[0041] For example, the ratios of cotton linter-derived cellulose acylate:wood pulp (coniferous)-derived cellulose acylate:wood pulp (broadleaf)-derived cellulose acylate can be 100:0:0, 90:10:0, 85:15:0, 50:50:0, 20:80:0, 10:90:0, 0:100:0, 0:0:100, 80:10:10, 85:0:15, or 40:30:30.
[0042] The cellulose acylate (A) according to the present invention can be produced by a known method. In general, the raw material cellulose is mixed with a specific organic acid (acetic acid, propionic acid, etc.), an acid anhydride (acetic anhydride, propionic anhydride, etc.), and a catalyst (sulfuric acid, etc.) to esterify the cellulose, and the reaction is continued until a triester of cellulose is produced. In the triester, three hydroxyl groups of the glucose unit are substituted with acyl groups of an organic acid. If two kinds of organic acids are used at the same time, a mixed ester type cellulose acylate, for example, cellulose acetate propionate or cellulose acetate butyrate, can be produced.
[0043] Next, the triester of cellulose is hydrolyzed as necessary to synthesize cellulose acylate (A) having a desired degree of acyl group substitution (2.6 to 3.0). After that, the cellulose acylate (A) is completed through steps such as filtration, precipitation, washing with water, dehydration, and drying.
[0044] The cellulose acylate (A) according to the present invention preferably has a pH in the range of 6 to 7 and an electrical conductivity in the range of 1 to 100 μS / cm when 1 g of the cellulose acylate (A) is added to 20 ml of pure water (electrical conductivity of 0.1 μS / cm or less, pH 6.8) and stirred at 25° C. for 1 hour under a nitrogen atmosphere.
[0045] The cellulose acylate (A) according to the present invention can be synthesized by referring to the method described in JP-A-10-45804.
[0046] <Sugar ester (B)> The substrate for the laminated film of the present invention contains a sugar ester (B) other than the cellulose acylate (A).
[0047] The sugar moiety in the sugar ester (B) according to the present invention is preferably a residue of a sugar having 1 to 12 of at least one kind of pyranose ring or furanose ring. That is, the sugar ester (B) is preferably a compound obtained by esterifying a sugar having 1 to 12 of at least one kind of pyranose ring or furanose ring. The sugar to be esterified may be a monosaccharide or a polysaccharide in which 2 to 12 sugar structures are linked together.
[0048] Sugar ester (B) is a sugar ester in which hydrogen atoms in 70 to 100% of hydroxyl groups of such sugar are substituted with acyl groups. In other words, sugar ester (B) is a compound in which at least 70% of OH groups of the raw sugar are esterified. Hereinafter, in sugar ester (B), the ratio of hydrogen atoms of hydroxyl groups in the raw sugar substituted with acyl groups, i.e., the ratio of OH groups esterified, is referred to as "esterification rate".
[0049] The esterification rate of the sugar ester (B) is preferably 75% or more, more preferably 100%, of the OH groups present in the pyranose ring or furanose ring. When the esterification rate of the sugar ester (B) is 70% or more, good adhesion can be obtained between the substrate and the optical functional layer laminated on the substrate.
[0050] The content of the sugar ester (B) in the substrate according to the present invention is preferably 1 to 30 parts by mass, more preferably 5 to 20 parts by mass, per 100 parts by mass of the cellulose acylate (A). When the content of the sugar ester (B) is within the above range, the retardation value in the substrate is controlled, and the above condition (1-2) is easily satisfied.
[0051] Examples of the raw sugar in the sugar ester (B) include glucose, galactose, mannose, fructose, xylose, or arabinose, lactose, sucrose, nystose, 1F-fructosylnystose, stachyose, maltitol, lactitol, lactulose, cellobiose, maltose, cellotriose, maltotriose, raffinose, and kestose. Examples of the raw sugar in the sugar ester (B) also include gentiobiose, gentiotriose, gentiotetraose, xylotriose, and galactosylsucrose. It is particularly preferable that the raw sugar in the sugar ester (B) contains both a pyranose ring and a furanose ring.
[0052] Preferred examples of the sugar as the raw material in the sugar ester (B) include glucose, sucrose, kestose, nystose, 1F-fructosylnystose, stachyose, etc., with glucose and sucrose being preferred, and sucrose being more preferred.
[0053] In the sugar ester (B), 70 to 100% of the hydrogen atoms of the OH groups of the raw sugar are substituted with acyl groups. There are no particular limitations on the acyl groups, so long as they are acyl groups represented by RC(=O)- (R is a monovalent hydrocarbon group). R may be an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, or an aromatic hydrocarbon group.
[0054] Sugar ester (B) is, for example, a compound obtained by esterifying the sugar exemplified above with a monocarboxylic acid represented by RC(=O)-OH (R is the same as above) in order to introduce the acyl group into the sugar. There is no particular limitation on the monocarboxylic acid used for esterification, and known aliphatic monocarboxylic acids, alicyclic monocarboxylic acids, aromatic monocarboxylic acids, etc. can be used. One type of monocarboxylic acid may be used alone, or two or more types may be used in combination.
[0055] Preferred examples of aliphatic monocarboxylic acids include saturated fatty acids such as acetic acid, propionic acid, butyric acid, isobutyric acid, valeric acid, caproic acid, enanthic acid, caprylic acid, pelargonic acid, capric acid, 2-ethyl-hexanecarboxylic acid, undecylic acid, lauric acid, tridecylic acid, myristic acid, pentadecylic acid, palmitic acid, heptadecylic acid, stearic acid, nonadecanoic acid, arachidic acid, behenic acid, lignoceric acid, cerotic acid, heptacosanoic acid, montanic acid, melissic acid, and lacteric acid; and unsaturated fatty acids such as undecylenic acid, oleic acid, sorbic acid, linoleic acid, linolenic acid, arachidonic acid, and octenoic acid.
[0056] Preferred examples of the alicyclic monocarboxylic acid include cyclopentane carboxylic acid, cyclohexane carboxylic acid, cyclooctane carboxylic acid, and derivatives thereof.
[0057] Preferred examples of the aromatic monocarboxylic acid include aromatic monocarboxylic acids in which an alkyl group or an alkoxy group has been introduced into the benzene ring of benzoic acid, such as benzoic acid and toluic acid, aromatic monocarboxylic acids having two or more benzene rings, such as cinnamic acid, benzilic acid, biphenylcarboxylic acid, naphthalenecarboxylic acid, and tetralincarboxylic acid, and derivatives thereof.
[0058] More specifically, the aromatic monocarboxylic acid includes xylyl acid, hemerylic acid, mesitylene acid, prenylic acid, γ-isoduryl acid, jurylic acid, mesitoic acid, α-isoduryl acid, cumic acid, α-toluic acid, hydratropic acid, atropic acid, hydrocinnamic acid, salicylic acid, o-anisic acid, m-anisic acid, p-anisic acid, creosote acid, o-homosalicylic acid, m-homosalicylic acid, p-homosalicylic acid, o-pyrocatechuic acid, β-resorcylic acid, vanillic acid, isovanillic acid, veratric acid, o-veratric acid, gallic acid, asarone acid, mandelic acid, homoanisic acid, homovanillic acid, homoveratric acid, o-homoveratric acid, phthalonic acid, and p-coumaric acid; benzoic acid is particularly preferred.
[0059] As the sugar ester (B) in the present invention, an ester compound of an oligosaccharide can be used as long as the above-mentioned esterification rate is satisfied. Oligosaccharides are produced, for example, by reacting starch, sucrose, etc. with an enzyme such as amylase. Examples of preferred oligosaccharides include maltooligosaccharides, isomaltooligosaccharides, fructooligosaccharides, galactooligosaccharides, and xylooligosaccharides.
[0060] Examples of the sugar ester (B) include esters of compounds in which 1 to 12 of at least one kind of pyranose ring or furanose ring having a structure represented by the following general formula (B) are condensed.
[0061] [ka]
[0062] R in general formula (B) 11 ~R 15 , R 21 ~R 25 represents an acyl group having 2 to 22 carbon atoms or a hydrogen atom. m and n each represent an integer of 0 to 12, and m+n represents an integer of 1 to 12. In formula (B), R 11 ~R 15 and R 21 ~R 25The proportion of acyl groups having 2 to 22 carbon atoms relative to the total number of the above is 70 to 100%.
[0063] The acyl group is R 26 -C(=O)-(R 26 is an aliphatic saturated hydrocarbon group having 1 to 21 carbon atoms, or a phenyl group or benzyl group having 6 to 20 carbon atoms which may have a substituent. Of these, an acyl group represented by the structure: 26 is an acetyl group, R is a methyl group 26 is a phenyl group, a benzoyl group is preferred, and an acetyl group is particularly preferred.
[0064] Examples of the substituents on the phenyl or benzyl group include an alkyl group, an alkenyl group, an alkoxyl group, and a phenyl group, and these alkyl groups, alkenyl groups, and phenyl groups may further have a substituent. Oligosaccharide ester compounds can also be produced in the same manner as other sugar esters.
[0065] Specific examples of the sugar ester (B) according to the present invention are given below, but the present invention is not limited thereto. In the compounds shown in the structures below, in which the "average degree of substitution" is not shown under the substituent (acyl group), it indicates that 100% of the hydrogen atoms of the OH groups of the sugar are substituted with the substituent. As the sugar ester (B), the following compounds in which 70% or more of the hydrogen atoms of the OH groups are substituted with acyl groups are also preferred. For example, in compound 1, a compound in which 30% or less of R1 are hydrogen atoms is also preferred as being in the category of sugar ester (B).
[0066] In the compounds whose structures are shown below, when the "average substitution degree" is shown under the substituent (acyl group), it indicates that the hydrogen atom of the OH group of the sugar is substituted with the substituent (acyl group) at that substitution degree. For example, in compound 3, the average substitution degree is 7.0, which indicates that seven of the eight R3 are substituted with benzoyl groups and the remaining one is a hydrogen atom. In this case, the esterification rate is 7 / 8 = 87.5%. On the other hand, in compound 12, the average substitution degree is 8.0, which indicates that the eight R 12 This indicates that all are substituted with benzoyl groups. In this case, the esterification rate is 8 / 8 = 100%.
[0067] [ka]
[0068] [ka]
[0069] [ka]
[0070] [ka]
[0071] [ka]
[0072] [ka]
[0073] [ka]
[0074] [ka]
[0075] The sugar ester (B) according to the present invention can be produced by reacting the above-mentioned sugar, for example, a sugar having 1 to 12 of at least one of pyranose rings or furanose rings, with an acylating agent (also called an esterifying agent). Examples of the acylating agent include acid halides or acid anhydrides of the above-mentioned various monocarboxylic acids. Specifically, when the acyl group is an acetyl group, acetyl chloride, acetic anhydride, etc., can be used, and when the acyl group is a benzoyl group, benzyl chloride, benzoic anhydride, etc. can be used.
[0076] In the esterification of sugar, the degree of substitution and the esterification rate of the resulting sugar ester vary slightly between molecules and have a distribution. The distribution of the degree of substitution and the esterification rate of the sugar ester can be achieved by adjusting the amount of the acylating agent, the timing of addition, and the esterification reaction time. By mixing sugar esters with different degrees of substitution and esterification rates, or by mixing pure isolated compounds with different degrees of substitution and esterification rates, a sugar ester (B) with a desired esterification rate (70 to 100%) can be prepared. The adjustment of the esterification rate will be specifically explained below using the reaction of esterifying sucrose with benzoic anhydride as an example.
[0077] (Synthesis Example: Synthesis of Sugar Ester (B) According to the Present Invention) [ka]
[0078] The esterification reaction of sucrose with benzoic anhydride was carried out as follows: 34.2 g (0.1 mol) of sucrose (sucrose), 135.6 g (0.6 mol) of benzoic anhydride, and 284.8 g (3.6 mol) of pyridine were charged into a four-head flask equipped with a stirrer, a reflux condenser, a thermometer, and a nitrogen gas inlet tube, and the mixture was heated while bubbling nitrogen gas from the nitrogen gas inlet tube with stirring, and the esterification reaction was carried out at 70°C for 5 hours.
[0079] Next, the pressure inside the Kolbe was reduced to 4×10 2 Pa or less, and after distilling off the excess pyridine at 60°C, the pressure inside the Kolbe was reduced to 1.3×10 Pa or less, the temperature was raised to 120°C, and benzoic anhydride and most of the produced benzoic acid were distilled off. Then, 1 L of toluene and 300 g of a 0.5 mass% aqueous sodium carbonate solution were added, stirred at 50°C for 30 minutes, allowed to stand, and the toluene layer was separated. Finally, 100 g of water was added to the separated toluene layer, washed with water at room temperature for 30 minutes, the toluene layer was separated, and under reduced pressure (4×10 2 Pa or less), toluene was distilled off at 60°C to obtain sugar ester 1, which is a mixture of compounds A-1, A-2, A-3, A-4, A-5, etc.
[0080] When the obtained mixture was analyzed by high performance liquid chromatography-mass spectrometry (HPLC-MS), A-1 was 1.2 mass%, A-2 was 13.2 mass%, A-3 was 14.2 mass%, A-4 was 35.4 mass%, and A-5, etc. was 40.0 mass%. The average degree of substitution was 5.2 and the esterification rate was 65%.
[0081] Note that A-5, etc. means a mixture of all components with a degree of substitution of 4 or less, that is, compounds with degrees of substitution of 4, 3, 2, and 1. Also, the average degree of substitution and the esterification rate were calculated with A-5, etc. having a degree of substitution of 4. The measurement conditions of HPLC-MS are as follows.
[0082] <Measurement Conditions of HPLC-MS> 1) LC section Apparatus: Column oven (JASCO CO-965), detector (JASCO UV-970-240nm), pump (JASCO PU-980), degasser (JASCO DG-980-50) manufactured by JASCO Corporation Column: Inertsil ODS-3, particle size 5μm, 4.6×250mm (manufactured by GL Sciences Inc.) Column temperature: 40°C Flow rate: 1 ml / min Mobile phase: THF (1% acetic acid): H2O (50:50) Injection volume: 3 μl 2) MS section Apparatus: LCQ DECA (Thermo Quest, Inc.) Ionization method: Electrospray ionization (ESI) method Spray Voltage: 5kV Capillary temperature: 180℃ Vaporizer temperature: 450℃
[0083] Similarly, 158.2 g (0.70 mol), 146.9 g (0.65 mol), 135.6 g (0.60 mol), and 124.3 g (0.55 mol) of benzoic anhydride were reacted with an equal mole of pyridine to obtain sugar ester 2, sugar ester 3, and sugar ester 4, respectively, with the component compositions, average degrees of substitution, and esterification rates shown in Table I.
[0084] [Table 1]
[0085] Sugar esters 1 to 4 thus obtained as mixtures of sugar esters with different degrees of substitution are purified by column chromatography using silica gel to obtain A-1, A-2, A-3, A-4, A-5, etc., each having a purity of 100%.
[0086] In the present invention, for example, a sugar ester having a desired esterification rate (70 to 100%) (sugar ester 2 in Table I) is selected from the sugar esters 1 to 4 thus prepared to give sugar ester (B). Alternatively, sugar ester (B) having an esterification rate adjusted to 70 to 100% is obtained by adding a combination of A-1 to A-5 isolated above.
[0087] (Other Ingredients) The substrate of the laminated film of the present invention may contain other components besides the cellulose acylate (A) and the sugar ester (B) as necessary, within the range not impairing the effects of the present invention. Examples of other components include plasticizers, ultraviolet absorbers, antioxidants, fine particles (matting agents), surfactants, polymer electrolytes, conductive complexes, antistatic agents, antiblocking agents, lubricants, etc.
[0088] <Plasticizer> In the base material according to the present invention, a known plasticizer having a molecular weight of 10,000 or less can be used within a range that does not impair the effects of the present invention. The plasticizer is not particularly limited, but is preferably selected from polyvalent carboxylate-based plasticizers, glycolate-based plasticizers, phthalate-based plasticizers, fatty acid ester-based plasticizers, polyhydric alcohol ester-based plasticizers, and the like.
[0089] The polyhydric alcohol ester is an ester (alcohol ester) of a divalent or higher aliphatic polyhydric alcohol and a monocarboxylic acid, and is preferably a di- to 20-valent aliphatic polyhydric alcohol ester. The polyhydric alcohol ester preferably has an aromatic ring or a cycloalkyl ring in the molecule.
[0090] Preferred examples of the aliphatic polyhydric alcohol include ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, 1,2-propanediol, 1,3-propanediol, dipropylene glycol, tripropylene glycol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, dibutylene glycol, 1,2,4-butanetriol, 1,5-pentanediol, 1,6-hexanediol, hexanetriol, trimethylolpropane, pentaerythritol, trimethylolethane, xylitol, etc. Among them, triethylene glycol, tetraethylene glycol, dipropylene glycol, tripropylene glycol, sorbitol, trimethylolpropane, xylitol, etc. are preferred.
[0091] The monocarboxylic acid is not particularly limited and may be an aliphatic monocarboxylic acid, an alicyclic monocarboxylic acid, an aromatic monocarboxylic acid, or the like. In order to increase the moisture permeability of the film and make it difficult to volatilize, an alicyclic monocarboxylic acid or an aromatic monocarboxylic acid is preferable. The monocarboxylic acid may be one type or a mixture of two or more types. In addition, all of the OH groups contained in the aliphatic polyhydric alcohol may be esterified, or a part of them may be left as OH groups.
[0092] The aliphatic monocarboxylic acid is preferably a fatty acid having a straight or side chain with 1 to 32 carbon atoms. The number of carbon atoms in the aliphatic monocarboxylic acid is more preferably 1 to 20, and even more preferably 1 to 10. Examples of the aliphatic monocarboxylic acid include saturated fatty acids such as acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, enanthic acid, caprylic acid, pelargonic acid, capric acid, 2-ethyl-hexanoic acid, undecylic acid, lauric acid, tridecylic acid, myristic acid, pentadecylic acid, palmitic acid, heptadecylic acid, stearic acid, nonadecanoic acid, arachic acid, behenic acid, lignoceric acid, cerotic acid, heptacosanoic acid, montanic acid, melissic acid, and lacteric acid; and unsaturated fatty acids such as undecylenic acid, oleic acid, sorbic acid, linoleic acid, linolenic acid, and arachidonic acid. Among these, in order to enhance compatibility with cellulose acetate, acetic acid or a mixture of acetic acid and another monocarboxylic acid is preferred.
[0093] Examples of the alicyclic monocarboxylic acids include cyclopentane carboxylic acid, cyclohexane carboxylic acid, cyclooctane carboxylic acid, and the like.
[0094] Examples of aromatic monocarboxylic acids include benzoic acid; benzoic acid having one to three alkyl groups or alkoxy groups (e.g., methoxy groups or ethoxy groups) introduced into the benzene ring (e.g., toluic acid, etc.); and aromatic monocarboxylic acids having two or more benzene rings (e.g., biphenylcarboxylic acid, naphthalenecarboxylic acid, tetralincarboxylic acid, etc.), preferably benzoic acid.
[0095] The polycarboxylic acid ester is an ester of a polycarboxylic acid having 2 or more valences, preferably 2 to 20 valences, and an alcohol. The polycarboxylic acid is preferably an aliphatic polycarboxylic acid having 2 to 20 valences, an aromatic polycarboxylic acid having 3 to 20 valences, or an alicyclic polycarboxylic acid having 3 to 20 valences.
[0096] Examples of polycarboxylic acids include trivalent or higher aromatic polycarboxylic acids or derivatives thereof, such as trimellitic acid, trimesic acid, and pyromellitic acid; aliphatic polycarboxylic acids, such as succinic acid, adipic acid, azelaic acid, sebacic acid, oxalic acid, fumaric acid, maleic acid, and tetrahydrophthalic acid; and oxypolycarboxylic acids, such as tartaric acid, tartronic acid, malic acid, and citric acid. In order to suppress evaporation from the film, oxypolycarboxylic acids are preferred.
[0097] Examples of the alcohol include linear or side chain aliphatic saturated alcohols, linear or side chain aliphatic unsaturated alcohols, alicyclic alcohols, and aromatic alcohols. The number of carbon atoms in the aliphatic saturated alcohols or aliphatic unsaturated alcohols is preferably 1 to 32, more preferably 1 to 20, and further preferably 1 to 10. Examples of the alicyclic alcohols include cyclopentanol and cyclohexanol. Examples of the aromatic alcohols include benzyl alcohol and cinnamyl alcohol.
[0098] The molecular weight of the polycarboxylic acid ester is not particularly limited, but is preferably in the range of 300 to 1000, and more preferably in the range of 350 to 750. From the viewpoint of suppressing bleed-out, the molecular weight of the polycarboxylic acid ester plasticizer is preferably larger; from the viewpoints of moisture permeability and compatibility with cellulose acetate, the molecular weight is preferably smaller.
[0099] Examples of polycarboxylic acid esters include triethyl citrate, tributyl citrate, acetyl triethyl citrate (ATEC), acetyl tributyl citrate (ATBC), benzoyl tributyl citrate, acetyl triphenyl citrate, acetyl tribenzyl citrate, dibutyl tartrate, diacetyl dibutyl tartrate, tributyl trimellitate, tetrabutyl pyromellitate, and the like.
[0100] The polycarboxylic acid ester may be a phthalic acid ester. Examples of the phthalic acid ester include diethyl phthalate, dimethoxyethyl phthalate, dimethyl phthalate, dioctyl phthalate, dibutyl phthalate, di-2-ethylhexyl phthalate, dioctyl phthalate, dicyclohexyl phthalate, and dicyclohexyl terephthalate.
[0101] Examples of glycolate include alkylphthalyl alkyl glycolates. Examples of alkylphthalyl alkyl glycolates include methylphthalyl methyl glycolate, ethylphthalyl ethyl glycolate, propylphthalyl propyl glycolate, butylphthalyl butyl glycolate, octylphthalyl octyl glycolate, methylphthalyl ethyl glycolate, ethylphthalyl methyl glycolate, ethylphthalyl propyl glycolate, methylphthalyl butyl glycolate, ethylphthalyl butyl glycolate, butylphthalyl methyl glycolate, butylphthalyl ethyl glycolate, propylphthalyl butyl glycolate, butylphthalyl propyl glycolate, methylphthalyl octyl glycolate, ethylphthalyl octyl glycolate, octylphthalyl methyl glycolate, octylphthalyl ethyl glycolate, etc., and preferably ethylphthalyl ethyl glycolate.
[0102] The ester plasticizers include fatty acid esters, citrate esters, phosphate esters, and the like.
[0103] Examples of fatty acid esters include butyl oleate, methylacetyl ricinoleate, and dibutyl sebacate, etc. Examples of citrate esters include acetyltrimethyl citrate, acetyltriethyl citrate, and acetyltributyl citrate, etc. Examples of phosphoric acid esters include triphenyl phosphate, tricresyl phosphate, cresyl diphenyl phosphate, octyl diphenyl phosphate, biphenyl diphenyl phosphate, trioctyl phosphate, and tributyl phosphate, etc., and preferably triphenyl phosphate.
[0104] The plasticizer may be used alone or in combination of two or more. The content of the plasticizer is preferably in the range of 1 to 20 parts by mass, more preferably in the range of 1.5 to 15 parts by mass, based on 100 parts by mass of the cellulose acylate (A). When the content of the plasticizer is within the above range, the effect of imparting plasticity can be exhibited, and the resistance to exudation of the plasticizer from the substrate is also excellent.
[0105] <Ultraviolet absorbing agent> When the substrate according to the present invention is used as a laminate film as a retardation film arranged on the front side (viewing side) of a liquid crystal display device, it is preferable that the substrate contains an ultraviolet absorbing agent from the viewpoint of improving light resistance. The ultraviolet absorbing agent aims to improve light resistance by absorbing ultraviolet rays of 400 nm or less, and the transmittance at a wavelength of 370 nm is preferably 10% or less, more preferably 5% or less, and even more preferably 2% or less.
[0106] The ultraviolet absorbents preferably used in the present invention are benzotriazole-based ultraviolet absorbents, benzophenone-based ultraviolet absorbents, and triazine-based ultraviolet absorbents, and particularly preferred are benzotriazole-based ultraviolet absorbents and benzophenone-based ultraviolet absorbents.
[0107] For example, there are 5-chloro-2-(3,5-di-sec-butyl-2-hydroxylphenyl)-2H-benzotriazole, (2-2H-benzotriazol-2-yl)-6-(straight-chain and side-chain dodecyl)-4-methylphenol, 2-hydroxy-4-benzyloxybenzophenone, 2,4-benzyloxybenzophenone, etc., and also Tinuvins such as Tinuvin 109, Tinuvin 171, Tinuvin 234, Tinuvin 326, Tinuvin 327, Tinuvin 328, Tinuvin 928, etc., all of which are commercially available products manufactured by BASF Japan Ltd. and can be preferably used. Among these, halogen-free ones are preferred.
[0108] In addition, discotic compounds such as compounds having a 1,3,5 triazine ring are also preferably used as ultraviolet absorbents.
[0109] When the substrate according to the present invention contains an ultraviolet absorbent, it may contain one or more kinds thereof, and preferably contains two or more kinds thereof.
[0110] As the ultraviolet absorbing agent, a polymeric ultraviolet absorbing agent can also be preferably used, and in particular, the polymer type ultraviolet absorbing agent described in JP-A-6-148430 is preferably used.
[0111] The ultraviolet absorbent may be added by dissolving it in an alcohol such as methanol, ethanol, or butanol, or an organic solvent such as methylene chloride, methyl acetate, acetone, or dioxolane, or a mixture thereof, and then adding the dissolved ultraviolet absorbent to the dope described below, or by directly adding the ultraviolet absorbent to the dope composition.
[0112] Inorganic powders that do not dissolve in organic solvents are dispersed in the organic solvent using a dissolver or a sand mill before being added to the dope.
[0113] The amount of the ultraviolet absorber used in the substrate varies depending on the type of ultraviolet absorber, the conditions of use, etc., but when the dry film thickness of the substrate is 15 to 50 μm, the amount is preferably in the range of 0.5 to 10 mass % relative to the substrate, and more preferably in the range of 0.6 to 4 mass %.
[0114] <Antioxidants> Antioxidants are also called anti-deterioration agents. When liquid crystal display devices are placed in high humidity and high temperature conditions, the base material may deteriorate.
[0115] The antioxidant has the role of delaying or preventing decomposition of the base material due to, for example, halogens in the residual solvent in the base material or phosphoric acid in the phosphoric acid-based plasticizer, and is therefore preferably contained in the base material.
[0116] As such an antioxidant, a hindered phenol-based compound is preferably used, for example, 2,6-di-t-butyl-p-cresol, pentaerythrityl-tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], triethylene glycol-bis[3-(3-t-butyl-5-methyl-4-hydroxyphenyl)propionate], 1,6-hexanediol-bis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], 2,4-bis-(n-octylthio)-6-(4-hydroxy-3,5-di-t-butyl)propionate, ethyl anilino)-1,3,5-triazine, 2,2-thio-diethylenebis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, N,N'-hexamethylenebis(3,5-di-t-butyl-4-hydroxy-hydrocinnamamide), 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, tris-(3,5-di-t-butyl-4-hydroxybenzyl)-isocyanurate, and the like can be mentioned.
[0117] In particular, 2,6-di-t-butyl-p-cresol, pentaerythrityl-tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], and triethylene glycol-bis[3-(3-t-butyl-5-methyl-4-hydroxyphenyl)propionate] are preferred. In addition, for example, hydrazine-based metal deactivators such as N,N'-bis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionyl]hydrazine and phosphorus-based processing stabilizers such as tris(2,4-di-t-butylphenyl)phosphite may be used in combination.
[0118] These antioxidants may be used alone or in combination of two or more. The amount of the antioxidant added to the substrate is preferably in the range of 1 ppm by mass to 1.0% by mass, more preferably 10 to 1000 ppm by mass, based on the mass of the cellulose acylate (A).
[0119] <Fine particles (matte agent)> The substrate in the laminated film of the present invention may further contain fine particles (matting agent) as necessary in order to enhance the slipperiness of the surface.
[0120] The fine particles may be inorganic or organic fine particles. Examples of inorganic fine particles include silicon dioxide (silica), titanium dioxide, aluminum oxide, zirconium oxide, calcium carbonate, calcium carbonate, talc, clay, calcined kaolin, calcined calcium silicate, hydrated calcium silicate, aluminum silicate, magnesium silicate, and calcium phosphate. Among them, silicon dioxide and zirconium oxide are preferred, and in order to reduce the increase in haze of the obtained substrate, silicon dioxide is more preferred.
[0121] Examples of silicon dioxide fine particles include Aerosil R972, R972V, R974, R812, 200, 200V, 300, R202, OX50, TT600, NAX50 (all manufactured by Nippon Aerosil Co., Ltd.), Sea Hoster KE-P10, KE-P30, KE-P50, KE-P100 (all manufactured by Nippon Shokubai Co., Ltd.), etc. Among them, Aerosil R972V, NAX50, Sea Hoster KE-P30, etc. are particularly preferred because they reduce the friction coefficient while keeping the turbidity of the obtained base material low.
[0122] The primary particle diameter of the fine particles is preferably in the range of 5 to 50 nm, and more preferably in the range of 7 to 20 nm. The larger the primary particle diameter, the greater the effect of increasing the slipperiness of the obtained substrate, but the greater the tendency for the transparency to decrease. Therefore, the fine particles may be contained as secondary aggregates having a particle diameter in the range of 0.05 to 0.3 μm. The size of the primary particles or secondary aggregates of the fine particles can be determined by observing the primary particles or secondary aggregates at a magnification of 500,000 to 2,000,000 times with a transmission electron microscope, and calculating the average particle diameter of 100 primary particles or secondary aggregates.
[0123] These fine particles may be used alone or in combination of two or more kinds. The content of the fine particles in the substrate is preferably in the range of 0.05 to 1.0 part by mass, more preferably in the range of 0.1 to 0.8 part by mass, based on 100 parts by mass of the cellulose acylate (A).
[0124] <Method of manufacturing the substrate> The substrate of the laminated film of the present invention can be produced by a conventional method such as inflation, T-die, calendar, cutting, casting, emulsion, hot press, etc. From the viewpoints of suppressing coloring, foreign matter defects, and optical defects such as die lines, the film production method can be selected from solution casting and melt casting, and the solution casting method is particularly preferred in order to obtain a uniform surface.
[0125] [Solution Casting Film Forming Method] The case where the substrate according to the present invention is produced by a solution casting method will be described below.
[0126] 1)Dissolution process The dissolution process is a process in which the cellulose acylate (A) and sugar ester (B), as well as other components added as necessary, are dissolved or dispersed in an organic solvent mainly consisting of a good solvent for the cellulose acylate (A) and sugar ester (B) in a dissolution vessel while stirring to form a dope, or a process in which a solution of the cellulose acylate (A) is mixed with a solution (dispersion) of the sugar ester (B) of the present invention and other components added as necessary to form a dope, which is the main solution.
[0127] The organic solvent can be used without any limitation as long as it can dissolve the cellulose acylate (A) and the sugar ester (B) and can also dissolve or disperse the other components described above.
[0128] For example, examples of chlorine-based organic solvents include methylene chloride, and examples of non-chlorine-based organic solvents include methyl acetate, ethyl acetate, amyl acetate, acetone, tetrahydrofuran, 1,3-dioxolane, 1,4-dioxane, cyclohexanone, ethyl formate, 2,2,2-trifluoroethanol, 2,2,3,3-hexafluoro-1-propanol, 1,3-difluoro-2-propanol, 1,1,1,3,3,3-hexafluoro-2-methyl-2-propanol, 1,1,1,3,3,3-hexafluoro-2-propanol, 2,2,3,3,3-pentafluoro-1-propanol, and nitroethane. Of these, methylene chloride, methyl acetate, ethyl acetate, and acetone can be preferably used.
[0129] In addition to the organic solvent, the dope preferably contains 1 to 40% by mass of a linear or branched aliphatic alcohol having 1 to 4 carbon atoms. When the ratio of the alcohol in the dope is high, the web gels and becomes easy to peel off from the metal support, and when the ratio of the alcohol is low, it also plays a role in promoting the dissolution of the cellulose acylate (A), the sugar ester (B) and other components in the non-chlorinated organic solvent system.
[0130] In particular, it is preferable that the dope is prepared by dissolving or dispersing cellulose acylate (A), sugar ester (B) and other components in a total amount of at least 15 to 45 mass % in a solvent containing methylene chloride and a linear or branched aliphatic alcohol having 1 to 4 carbon atoms.
[0131] Examples of the linear or branched aliphatic alcohol having 1 to 4 carbon atoms include methanol, ethanol, n-propanol, iso-propanol, n-butanol, sec-butanol, and tert-butanol. Among these, ethanol is preferred because of the stability of the dope, the relatively low boiling point, and the good drying property.
[0132] The dissolution or dispersion of cellulose acylate (A), sugar ester (B) and other components can be carried out by various dissolution methods such as normal pressure, pressure below the boiling point of main solvent, pressure above the boiling point of main solvent, cooling dissolution method as described in JP-A-9-95544, JP-A-9-95557 or JP-A-9-95538, pressure above the boiling point of main solvent, etc., and the method of carrying out at high pressure as described in JP-A-11-21379 is particularly preferred. The dope during or after dissolution of each component is preferably filtered with filter material, degassed, and sent to the next process by liquid pump.
[0133] For filtration, it is preferable to use a filter medium with a collection particle size of 0.5 to 5 μm and a filtration time of 10 to 25 sec / 100 ml.
[0134] In this method, the aggregates remaining during particle dispersion and the aggregates generated during the addition of the main dope can be removed by using a filter with a collection particle size of 0.5 to 5 μm and a filtration time of 10 to 25 sec / 100 ml. The particle concentration in the main dope is sufficiently low compared to the additive liquid, so the aggregates do not stick together during filtration, causing a sudden increase in filtration pressure.
[0135] 2) Casting process In this process, the dope is sent to a pressure die through a liquid sending pump (e.g., a pressure type fixed quantity gear pump) and cast from the pressure die slit onto a casting position on a metal support such as an endless metal belt, e.g., a stainless steel belt, which moves indefinitely, or a rotating metal drum.
[0136] A pressure die is preferred because it is possible to adjust the slit shape of the die nozzle and to easily make the film thickness uniform. Pressure dies include coat hanger dies and T-dies, and any of them are preferably used. The surface of the metal support is a mirror finish. In order to increase the film production speed, two or more pressure dies may be provided on the metal support, and the dope amount may be divided and layered. Alternatively, it is also preferred to obtain a film with a laminated structure by a co-casting method in which multiple dopes are cast simultaneously.
[0137] 3) Solvent evaporation process In this process, the web (the dope is cast onto the casting support and the dope film formed is called the web) is heated on the casting support to evaporate the solvent.
[0138] The solvent can be evaporated by blowing air from the web side and / or by transferring heat from the back side of the support using a liquid, or by transferring heat from the front and back sides using radiant heat, but the back side liquid heat transfer method is preferred because of its high drying efficiency. A combination of these methods is also preferably used. It is preferable to dry the web on the support after casting in an atmosphere of 20 to 100°C on the support. To maintain the atmosphere at 20 to 100°C, it is preferable to apply hot air at this temperature to the top surface of the web or heat it by means of infrared rays or the like.
[0139] From the viewpoints of surface quality, moisture permeability, and releasability, it is preferable to peel the web from the support within 30 to 120 seconds.
[0140] Depending on the conditions of the solvent evaporation process, the physical properties (1-2) above may be affected when the substrate is used. Planar orientation is likely to progress in the web in the early stages of the solvent evaporation process, so the slope T of the out-of-plane retardation tends to increase by lowering the solvent evaporation rate at a low temperature. Conversely, the slope T of the out-of-plane retardation tends to decrease by increasing the solvent evaporation rate.
[0141] Therefore, for example, a method of performing a heat treatment at a low temperature of about 20 to 50° C. for about 20 to 60 seconds at the beginning of the solvent evaporation process, and then performing a heat treatment at a high temperature of about 50 to 70° C. until the amount of residual solvent at the time of peeling the web falls within an appropriate range is preferable from the viewpoint of setting the gradient T of the out-of-plane retardation within the above range (1-2).
[0142] The amount of residual solvent in the web at the time of peeling the web from the metal support in the peeling step described below is preferably in the range of about 20 to 80 mass %, depending on the strength of the drying conditions, the length of the metal support, etc. If peeling is performed at a time when the amount of residual solvent is greater, if the web is too soft, the flatness at the time of peeling is lost and wrinkles or vertical streaks are likely to occur due to the peel tension, so the amount of residual solvent at the time of peeling is determined taking into account the economic speed and quality. The amount of residual solvent in the web is defined by the following formula.
[0143] Residual solvent amount (mass%)=(mass of web before heat treatment−mass of web after heat treatment) / (mass of web after heat treatment)×100 The heat treatment for measuring the amount of residual solvent refers to a heat treatment at 140° C. for 1 hour.
[0144] 4) Peeling process This is a process in which the solvent is evaporated from the web on the metal support until the residual solvent amount in the web reaches the appropriate amount, for example, 20 to 80% by mass, preferably 20 to 30% by mass, and the web is then peeled off at a peeling position. The peeled web is sent to the next process.
[0145] The peel tension when peeling the metal support and the web is usually within the range of 160 to 245 N / m, but if wrinkles are likely to occur during peeling, it is preferable to peel the web with a tension of 190 N / m or less.
[0146] In the present invention, the temperature at the peeling position on the metal support is preferably within the range of -50 to 40°C, more preferably within the range of 10 to 40°C, and most preferably within the range of 15 to 30°C.
[0147] 5) Drying and stretching process After peeling, the web is dried using a drying device in which the web is conveyed by alternately passing it through a plurality of rollers arranged in the drying device, and / or a tenter stretching device in which both ends of the web are clipped with clips and conveyed.
[0148] The drying method generally involves blowing hot air on both sides of the web, but there is also a method of heating by applying microwaves instead of air. Drying that is too rapid can easily damage the flatness of the finished substrate. Drying at high temperatures should be started when the residual solvent is about 8 mass % or less. Overall, drying is generally carried out within the range of about 40 to 250°C. It is particularly preferable to dry within the range of 40 to 200°C.
[0149] The web is preferably stretched in a direction perpendicular to the conveying direction (casting direction, MD direction) (width direction, TD direction) so that the thickness of the substrate after stretching is within the range of 10 to 50 μm, at a temperature range of (Tg+15) to (Tg+50) ° C., where Tg is the glass transition temperature of the substrate. At temperatures below (Tg+15) ° C., retardation is likely to occur, and the stretching stress increases, so that the haze tends to increase. If stretching is performed at a temperature above (Tg+50) ° C., breakage may occur, flatness may deteriorate, and the substrate itself may become more strongly colored, so that the quality (optical properties) of the retardation film may not be maintained. It is more preferable to perform the stretching temperature in the range of (Tg+20) to (Tg+40) ° C.
[0150] The glass transition temperature Tg referred to here is the midpoint glass transition temperature (Tmg) measured at a heating rate of 20° C. / min using a commercially available differential scanning calorimeter and determined in accordance with JIS K7121 (1987).
[0151] Specifically, the glass transition temperature Tg of the substrate is measured according to JIS K7121 (1987) using a differential scanning calorimeter DSC220 manufactured by Seiko Instruments Inc.
[0152] About 10 mg of a substrate sample is set, and under conditions of a nitrogen flow rate of 50 ml / min, the temperature is raised from room temperature to 250°C at 20°C / min and held for 10 minutes (1st scan), then the temperature is lowered to 30°C at a rate of 20°C / min and held for 10 minutes (2nd scan), and then the temperature is raised further to 250°C at 20°C / min (3rd scan), and a DSC curve is created, and the glass transition temperature Tg can be determined from the obtained DSC curve of the 3rd scan.
[0153] In the present invention, it is preferable to experimentally prepare a sample in advance using the material constituting the substrate, and stretch the sample substrate in the above-mentioned temperature range with respect to the measured Tg.
[0154] When a tenter stretching machine is used for stretching, it is preferable to use a machine that can independently control the gripping length (the distance from the start of gripping to the end of gripping) of the web on the left and right sides by the left and right gripping means of the tenter stretching machine. It is also preferable to intentionally create zones with different temperatures in the stretching process to improve flatness.
[0155] It is also preferable to provide a neutral zone between the different temperature zones so that each zone does not interfere with the other.
[0156] The stretching operation may be divided into multiple stages, and it is particularly preferable to perform biaxial stretching in the casting direction and the width direction. When performing biaxial stretching, simultaneous biaxial stretching may be performed or it may be performed stepwise. The stretching ratio, the sum of the stretching ratio in the casting direction and the width direction, is preferably within a range of 1.1 to 4 times, preferably 1.2 to 3 times, the original width of the web.
[0157] In this case, the term "stepwise" means, for example, that stretching in different directions can be performed sequentially, or that stretching in the same direction can be divided into multiple steps and stretching in a different direction can be added to any of the steps. That is, for example, the following stretching steps are also possible.
[0158] Stretch in casting direction → Stretch in width direction → Stretch in casting direction → Stretch in casting direction Stretch in width direction → Stretch in width direction → Stretch in casting direction → Stretch in casting direction Simultaneous biaxial stretching also includes stretching in one direction and contracting the other direction by relaxing tension. The preferred stretching ratio for simultaneous biaxial stretching is 1.01 to 1.5 times the original width in both the transverse direction and the casting direction. From the viewpoint of reducing the retardation value, it is particularly preferred to stretch in the transverse direction at a ratio of 1.01 to 1.2 times the original width of the film, more preferably 1.05 to 1.1 times.
[0159] When drying and stretching are performed using a tenter stretching apparatus, the residual solvent content of the web is preferably in the range of 20 to 30% by mass when it is passed through the tenter stretching apparatus, and it is preferable to dry the web while passing it through the tenter stretching apparatus until the residual solvent content of the web becomes 15% by mass or less.
[0160] In the tenter stretching apparatus, the residual solvent content of the web at the start of stretching is preferably 1 to 15 mass%, more preferably 2 to 10 mass%, and is preferably dried until the residual solvent content at the winding step is 2 mass% or less, more preferably 0.4 mass% or less.
[0161] In a tenter stretching apparatus, it is preferable that the temperature distribution in the width direction of the atmosphere is small from the viewpoint of improving the uniformity of the substrate, and the temperature distribution in the width direction in the tenter stretching apparatus is preferably within ±5°C, more preferably within ±2°C, and most preferably within ±1°C.
[0162] 6) Embossing process The substrate according to the present invention is thin, preferably having a thickness in the range of 10 to 50 μm, and therefore there is a concern that the substrate may slip when stored in a roll and that the optical quality may deteriorate, but these problems can be effectively prevented by embossing. Note that embossing is an optional step.
[0163] The embossed portion is a pattern of a certain width consisting of continuous minute projections and recesses on the substrate before the long film is wound up, in order to prevent the back and front surfaces of the wound film from completely adhering to each other. When one surface of the substrate (e.g., the upper surface) is protruded in a convex shape, a relative recess is formed on the other surface of the substrate (e.g., the lower surface) in correspondence with the convex shape. This serves to prevent the substrates from completely or partially adhering to each other when wound up, affecting the condition of the substrate surfaces and causing failures.
[0164] 7) Winding process After the residual solvent content in the web is reduced to 2% by mass or less, the web is wound up as a substrate by a winder. By reducing the residual solvent content to 0.4% by mass or less, a substrate with good dimensional stability can be obtained. It is particularly preferable to wind the web when the residual solvent content is in the range of 0.00 to 0.10% by mass.
[0165] The winding method may be any commonly used method, such as a constant torque method, a constant tension method, a taper tension method, or a program tension control method with constant internal stress, and any of these may be used appropriately.
[0166] According to the above method, the substrate of the present invention can be obtained as, for example, a long film. Specifically, the substrate can be obtained as a long film having a length of about 100 m to 10,000 m, and more preferably as a roll of the substrate having a length of 5,000 m or more. The substrate preferably has a width of 1 to 4 m, and more preferably 1.4 to 3 m. The substrate of the present invention preferably has a thickness in the range of 10 to 50 μm, and more preferably 20 to 40 μm.
[0167] <Characteristics of the substrate> (Retardation value) The substrate according to the present invention preferably has an in-plane retardation Ro590 defined by the following formula (i) in the range of 0 to 10 nm, and an out-of-plane retardation R590 defined by the following formula (ii) in the range of -20 to 20 nm, as measured with light having a wavelength of 590 nm in an environment of a temperature of 23°C and a relative humidity of 55%.
[0168] Formula (i): Ro = (n x -n y )×d(nm) Equation (ii): R={(n x +n y ) / 2-n z}×d(nm) [In the formula (i) and the formula (ii), n x represents the refractive index in the direction x where the refractive index is maximum in the in-plane direction of the film. y represents the refractive index in the in-plane direction of the film, in the direction y perpendicular to the direction x. z represents the refractive index in the thickness direction z of the film. d represents the thickness of the film (nm).
[0169] These phase differences (retardation values) can be measured using an automatic birefringence meter KOBRA-WPR (Oji Scientific Instruments).
[0170] The substrate according to the present invention satisfies the above (1-2) with respect to the out-of-plane retardation. That is, the value T (slope T of the out-of-plane retardation) calculated based on the out-of-plane retardation R650 measured with light having a wavelength of 650 nm and the out-of-plane retardation R450 measured with light having a wavelength of 450 nm according to the above formula (1) is within the range of 0.040 to 0.055. The slope T of the out-of-plane retardation is preferably within the range of 0.045 to 0.050.
[0171] The out-of-plane retardation R650 and the out-of-plane retardation R450 can be measured in the same manner as the out-of-plane retardation R590, except that the measurement wavelengths are different.
[0172] By setting the gradient T of the out-of-plane retardation of the substrate within the above range, when the substrate is laminated with an optical functional layer to form the laminate film of the present invention, the laminate film can achieve the optical characteristic (3) above (1.1≦Rth450 / Rth550≦1.9).
[0173] (All Haze) The substrate according to the present invention preferably has a total haze of less than 1%, more preferably 0.5% or less, and even more preferably 0.2% or less. If the haze is less than 1%, the transparency of the substrate does not decrease, and when laminated with an optical functional layer to form the laminate film of the present invention, the laminate film functions sufficiently as an optical (retardation) film.
[0174] The total haze of the substrate can be measured using a haze meter NDH-2000 (manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with JIS K-7136. The light source of the haze meter can be a 5V9W halogen bulb, and the light receiving part can be a silicon photocell (with a relative visibility filter). The haze can be measured under conditions of 23°C and 55% RH.
[0175] (Total light transmittance) The substrate according to the present invention preferably has a total light transmittance of 90% or more, more preferably 93% or more. The practical upper limit is about 99%. In order to achieve excellent transparency represented by such total light transmittance, it is effective to avoid introducing additives or copolymerization components that absorb visible light, or to remove foreign matter in the raw material, for example, in the dope, by high-precision filtration to reduce the diffusion and absorption of light inside the substrate. In addition, it is effective to reduce the surface roughness of the substrate surface by reducing the surface roughness of the substrate surface by reducing the surface roughness of the substrate surface (cooling roller, calendar roller, drum, belt, coating substrate in solution film formation, transport roller, etc.) in film formation.
[0176] (optical functional layer) The optical functional layer contains a polymer containing fumaric acid ester polymerization units at a ratio of 90 mol % or more relative to the total polymerization units. In the polymer, 80 to 100% of the ester moieties of the fumaric acid ester polymerization units are isopropyl ester. Hereinafter, a polymer containing fumaric acid ester polymerization units at a ratio of 90 mol % or more relative to the total polymerization units and 80 to 100% of the ester moieties of the fumaric acid ester polymerization units are isopropyl ester is also referred to as "polymer (F)".
[0177] The optical functional layer may contain components other than the polymer (F) as necessary, within the scope of not impairing the effects of the present invention.
[0178] (Polymer (F)) The optical functional layer contains a polymer (F). The optical functional layer is composed of the polymer (F) except for other components that are optionally contained. The content of the polymer (F) in the optical functional layer is, for example, preferably 90% by mass or more, more preferably 95% by mass or more, and particularly preferably 100% by mass.
[0179] The polymer (F) used in the present invention is a polymer containing fumaric acid ester polymerization units in a ratio of 90 mol % or more based on the total polymerization units, and 80 to 100% of the ester moieties of the fumaric acid ester polymerization units are isopropyl esters. Here, the "polymerization units" are units derived from monomers constituting the polymer, and refer to units constituted by residues in the polymer of raw material monomers used to prepare the polymer.
[0180] In the polymer (F), the ratio of the fumaric acid ester polymerization units to the total polymerization units is preferably 95 mol% or more, more preferably 98 mol% or more, and particularly preferably 100 mol%. In the polymer (F), the ratio of isopropyl ester in the ester portion of the fumaric acid ester polymerization units is preferably 85 to 100%, more preferably 90 to 100%, and particularly preferably 100%.
[0181] In the polymerization unit of fumaric acid ester, the fumaric acid ester as a monomer from which the polymerization unit is derived may be a monoester in which only one of the two carboxyl groups in fumaric acid is esterified, or a diester in which both of the two carboxyl groups are esterified. In the polymer (F), it is preferable to use a fumaric acid diester. The ester portion of the fumaric acid ester used as a monomer contains an isopropyl ester, and the monomers are used in combination so that the ratio of isopropyl ester in the ester portion of the polymerization unit of fumaric acid ester in the entire polymer (F) is within the above range.
[0182] As the fumaric acid ester polymerized unit in the polymer (F), for example, a fumaric acid diester polymerized unit (a) represented by the following general formula (a) is preferable.
[0183] [ka]
[0184] In the general formula (a), R1 and R2 each independently represent an alkyl group having 1 to 12 carbon atoms, provided that 80 to 100% of the total number of R1 and R2 in the polymer (F) are isopropyl groups.
[0185] Hereinafter, the monomer that is the basis of the fumaric acid diester polymerization unit (a) is also referred to as "fumaric acid diester (a)", and R1 and R2 are also referred to as "ester group". The polymer (F) can be a polymer obtained by combining and polymerizing fumaric acid diesters (a1) to (a3) classified as follows in the fumaric acid diester (a) such that 80 to 100% of the ester groups are isopropyl groups. The proportion of isopropyl groups in the ester groups is preferably 85 to 100%, more preferably 90 to 100%, and particularly preferably 100%.
[0186] Fumaric acid diester (a1); both R1 and R2 are isopropyl groups. Fumaric acid diester (a2): one of R1 and R2 is an isopropyl group, and the other is an alkyl group having 1 to 12 carbon atoms other than an isopropyl group. Fumaric acid diester (a3): both R1 and R2 are alkyl groups having 1 to 12 carbon atoms other than an isopropyl group.
[0187] Here, examples of the alkyl group having 1 to 12 carbon atoms other than an isopropyl group in R1 and R2 include linear alkyl groups such as methyl, ethyl, n-propyl, n-butyl, n-pentyl, and n-hexyl groups, branched alkyl groups such as s-butyl, t-butyl, s-pentyl, t-pentyl, s-hexyl, and t-hexyl groups, and cyclic alkyl groups such as cyclopropyl, cyclopentyl, and cyclohexyl groups. These alkyl groups may be substituted with halogen groups such as fluorine and chlorine, ether groups, ester groups, or amino groups, within the scope of the present invention.
[0188] When fumaric acid diesters (a1) to (a3) are combined to obtain polymer (F), from the viewpoint of ease of production, it is preferable to combine fumaric acid diester (a1), i.e., diisopropyl fumarate and fumaric acid diester (a3) to obtain polymer (F). When diisopropyl fumarate and fumaric acid diester (a3) are used as monomers in the polymerization of polymer (F), 80 to 100% of the ester moieties of the polymerized units of fumaric acid ester in polymer (F) can be isopropyl ester by setting the molar percentage of diisopropyl fumarate to 80 to 100 mol% relative to the total molar amount of diisopropyl fumarate and fumaric acid diester (a3).
[0189] Examples of the fumaric acid diester (a3) include dimethyl fumarate, diethyl fumarate, di-n-propyl fumarate, di-n-butyl fumarate, di-n-pentyl fumarate, di-n-hexyl fumarate, di-s-butyl fumarate, di-t-butyl fumarate, di-s-pentyl fumarate, di-t-pentyl fumarate, di-s-hexyl fumarate, di-t-hexyl fumarate, dicyclopropyl fumarate, dicyclopentyl fumarate, dicyclohexyl fumarate, and the like, and dimethyl fumarate, diethyl fumarate, and the like are preferred.
[0190] In the polymer (F), examples of the polymerization units other than the fumaric acid ester polymerization units that may be contained in an amount of 10 mol % or less based on the total polymerization units include polymerization units based on the following monomers. In the polymer (F), a monomer that is the basis of the polymerization units other than the fumaric acid ester polymerization units is hereinafter also referred to as "monomer (b)".
[0191] Examples of the monomer (b) include one or more of styrenes such as styrene and α-methylstyrene; (meth)acrylic acid; (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 3-ethyl-3-oxetanylmethyl (meth)acrylate, and tetrahydrofurfuryl (meth)acrylate; vinyl esters such as vinyl acetate and vinyl propionate; acrylonitrile; methacrylonitrile; olefins such as ethylene and propylene; etc. In addition, "(meth)acrylic acid" refers to either acrylic acid or methacrylic acid or both.
[0192] The polymer (F) used in the present invention has a number average molecular weight (Mn) of 1×10 in terms of standard polystyrene obtained from an elution curve measured by gel permeation chromatography (GPC). 3 It is preferable that the thickness is 2×10 or more, and since it is an optically functional layer having excellent mechanical properties and excellent moldability during film formation, 4 More than 2×10 5 It is preferable that:
[0193] The polymer (F) used in the present invention may be produced by any method as long as the polymer (F) can be obtained, and may be produced, for example, by radical polymerization or radical copolymerization using a fumaric acid ester selected so that 80-100% of the ester moieties of the polymerized units of the fumaric acid ester in the resulting polymer (F) are isopropyl esters, and, if necessary, a monomer (b) that accounts for 10 mol% or less of the total monomers. As the fumaric acid ester, it is preferable to use a mixture of 80-100 mol% of diisopropyl fumarate and 0-20 mol% of fumaric acid diester (a3).
[0194] The radical polymerization method used can be any known polymerization method, such as bulk polymerization, solution polymerization, suspension polymerization, precipitation polymerization, emulsion polymerization, and the like.
[0195] Examples of polymerization initiators for carrying out radical polymerization include organic peroxides such as benzoyl peroxide, lauryl peroxide, octanoyl peroxide, acetyl peroxide, di-t-butyl peroxide, t-butylcumyl peroxide, dicumyl peroxide, t-butyl peroxyacetate, t-butyl peroxybenzoate, and t-butyl peroxypivalate; and azo initiators such as 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-butyronitrile), 2,2'-azobisisobutyronitrile, dimethyl-2,2'-azobisisobutyrate, and 1,1'-azobis(cyclohexane-1-carbonitrile).
[0196] Solvents that can be used in the solution polymerization method, suspension polymerization method, precipitation polymerization method, and emulsion polymerization method are not particularly limited, and examples thereof include aromatic solvents such as benzene, toluene, and xylene; alcohol solvents such as methanol, ethanol, propyl alcohol, and butyl alcohol; cyclohexane; dioxane; tetrahydrofuran (THF); acetone; methyl ethyl ketone; dimethylformamide; isopropyl acetate; water; and mixed solvents of these.
[0197] The polymerization temperature during radical polymerization can be appropriately set depending on the decomposition temperature of the polymerization initiator, and is generally preferably within the range of 40 to 150°C.
[0198] (Other Ingredients) The optical functional layer of the laminated film of the present invention may contain other components other than the polymer (F) as necessary within the range that does not impair the effects of the present invention. Examples of other components include ultraviolet absorbers, antioxidants, fine particles (matting agents), surfactants, polymer electrolytes, conductive complexes, antistatic agents, antiblocking agents, lubricants, etc.
[0199] The optical functional layer according to the present invention is preferably blended with an antioxidant to enhance thermal stability. Examples of the antioxidant include the hindered phenol-based antioxidants, phosphorus-based antioxidants, and other antioxidants as described above for the substrate, and these antioxidants may be used alone or in combination.
[0200] In the optical functional layer, it is preferable to use a hindered phenol-based antioxidant and a phosphorus-based antioxidant in combination because the antioxidant action is synergistically improved, and in this case, it is particularly preferable to mix 100 to 500 parts by mass of the phosphorus-based antioxidant with 100 parts by mass of the hindered phenol-based antioxidant. The amount of the antioxidant added in the optical functional layer is preferably 0.01 to 10 parts by mass, particularly preferably 0.5 to 1 part by mass, with respect to 100 parts by mass of the polymer (F).
[0201] Examples of the ultraviolet absorbing agent and the fine particles (matting agent) that can be contained in the optical functional layer include the same ultraviolet absorbing agent and the fine particles (matting agent) that can be contained in the above-mentioned base material.
[0202] <Method of manufacturing optical functional layer and laminated film> In the present invention, the optical functional layer is laminated with the above-mentioned substrate to form the laminated film of the present invention. The optical functional layer may be formed into a film shape alone, or may be formed into a layer shape on the substrate. When the optical functional layer is formed alone, the optical functional layer and the substrate are laminated, for example, using an adhesive. When the optical functional layer is formed into a layer shape on the substrate, the production of the optical functional layer and the lamination of the optical functional layer and the substrate are performed simultaneously.
[0203] In the case where the optical functional layer is formed into a film by itself, for example, the same manufacturing method as the manufacturing method of the substrate, such as an inflation method, a T-die method, a calendar method, a cutting method, a casting method, an emulsion method, a hot press method, etc. can be applied, and a solution casting method and a melt casting method can be selected as a preferred method, and in particular, the solution casting method is preferred in order to obtain a uniform surface.
[0204] The solution casting film-forming method is a method in which a solution (dope) in which the polymer (F) and other components added as necessary are dissolved in a solvent is cast onto a support, and then the solvent is removed by heating or the like to obtain a film. In the solution casting film-forming method, when a film having high transparency, thickness precision, and surface smoothness is formed, the solution viscosity of the dope is an extremely important factor, and is preferably 700 to 30,000 cps, and particularly preferably 1,000 to 10,000 cps.
[0205] The dope can be cast onto a support by, for example, the T-die method, doctor blade method, bar coater method, roll coater method, lip coater method, etc. In particular, the most common method industrially is to continuously extrude the dope from a die onto a belt-shaped or drum-shaped support. Supports that can be used include, for example, glass substrates; metal supports such as stainless steel and ferrotype; and plastic supports such as polyethylene terephthalate (PET) and triacetyl cellulose (TAC).
[0206] The dope extruded onto the support is heated or otherwise treated to remove the solvent, forming a film. In this manner, a film-like optical functional layer containing the polymer (F) is obtained. The film is peeled off from the support for use.
[0207] The melt casting film forming method is a molding method in which a mixture of the components of the optical functional layer containing the polymer (F) is melted in an extruder, extruded into a film from a slit in a T-die, and then taken up while being cooled by a roll or air.
[0208] The method of laminating the film-like optical functional layer and the substrate includes a method of laminating them using a known adhesive. When the film-like optical functional layer is produced as a roll body by the solution casting film forming method as described above and the substrate is produced as a roll body as described above, for example, they can be laminated using a known adhesive in a roll-to-roll continuous process.
[0209] When the optical functional layer is formed in a layer shape on the substrate, the optical functional layer can be produced by applying a liquid composition for forming the optical functional layer onto the substrate and drying it. At the same time, the optical functional layer and the substrate are laminated to obtain the laminated film of the present invention.
[0210] In this method, first, a solution (coating solution) is prepared by dissolving the polymer (F) and other components added as necessary in a solvent. In order to obtain an optical functional layer having high transparency, thickness precision, and surface smoothness, the viscosity of the coating solution is an extremely important factor, and is preferably 10 to 10,000 cps, and more preferably 10 to 5,000 cps.
[0211] Examples of the coating method include a doctor blade method, a bar coater method, a gravure coater method, a slot die coater method, a lip coater method, a comma coater method, etc. Industrially, the gravure coater method is generally used for thin film coating, and the comma coater method is generally used for thick film coating.
[0212] After coating on the substrate, the solvent is removed by heating, etc., to obtain an optical functional layer on the substrate. In the melt casting film forming method, a substrate is used as a support, and a film as an optical functional layer is formed on the substrate, thereby making it possible to obtain a laminated film.
[0213] Prior to laminating the substrate and the optical functional layer, the surface of the substrate to be laminated with the optical functional layer may be subjected to a treatment for facilitating adhesion, such as a plasma treatment or a corona discharge treatment.
[0214] The thickness of the optical functional layer in the laminate film of the present invention is determined by the retardation in the thickness direction of the optical functional layer, and is preferably 1 to 30 μm, more preferably 2 to 20 μm, and particularly preferably 2 to 10 μm.
[0215] <Characteristics of laminated film> (Retardation value) The laminated film of the present invention satisfies the above (3) regarding the out-of-plane retardation. That is, the ratio Rth450 / Rth550 of the out-of-plane retardation Rth450 measured with light having a wavelength of 450 nm to the out-of-plane retardation Rth550 measured with light having a wavelength of 550 nm for the laminated film is within the range of 1.1 to 1.9. Rth450 / Rth550 is preferably within the range of 1.2 to 1.7.
[0216] The out-of-plane retardation Rth450 and the out-of-plane retardation Rth550 can be measured in the same manner as the method for measuring the out-of-plane retardation of a substrate, except that the measurement wavelength is different.
[0217] The laminate film of the present invention has an out-of-plane retardation Rth550 in the range of preferably -30 to -15 nm, more preferably -25 to -18 nm, and an out-of-plane retardation Rth450 in the range of preferably -40 to -15 nm, more preferably -30 to -18 nm.
[0218] (All Haze) The laminated film of the present invention preferably has a total haze of less than 1%, more preferably 0.5% or less, and even more preferably 0.2% or less, measured in the same manner as the substrate. If the haze is less than 1%, the transparency of the laminated film does not decrease, and the film functions satisfactorily as an optical (retardation) film.
[0219] (Total light transmittance) The laminated film of the present invention preferably has a total light transmittance of 90% or more, more preferably 93% or more, as measured by the same method as for the substrate. The practical upper limit is about 99%.
[0220] <Other functional layers> The laminated film of the present invention may be provided with functional layers such as an antistatic layer, a backcoat layer, an antireflection layer, a slippery layer, an adhesive layer, an antiglare layer, and a barrier layer, depending on the application.
[0221] [Polarizing plate] The polarizing plate of the present invention is characterized in that it is obtained by laminating the laminate film of the present invention and a polarizer. The polarizing plate of the present invention has the laminate film of the present invention, and when used in a liquid crystal display device, the polarizing plate can ensure good visibility.
[0222] The polarizing plate of the present invention has, for example, a polarizer and the laminate film of the present invention arranged on one side of the polarizer. In this case, the polarizing plate may have a protective film on the other side of the polarizer. Alternatively, the polarizing plate may have the laminate film of the present invention on both sides of the polarizer.
[0223] Fig. 2 is a cross-sectional view showing an example of the configuration of a polarizing plate of the present invention. As shown in Fig. 2, a polarizing plate 20 has a polarizer 11, a laminate film 10 arranged on one surface of the polarizer 11, and a protective film 12 arranged on the other surface. The laminate film 10 is formed by laminating a substrate 1 and an optically functional layer 2, and is arranged so that the substrate 1 side faces one surface of the polarizer 11. The polarizer 11, the laminate film 10, and the protective film 12 are bonded together via an optional adhesive layer (not shown).
[0224] <Polarizer> A polarizer, which is a main component of a polarizing plate, is an element that transmits only light polarized in a certain direction, and a representative polarizer currently known is a polyvinyl alcohol polarizing film. There are two types of polyvinyl alcohol polarizing film: one in which the film is dyed with iodine and one in which the film is dyed with a dichroic dye.
[0225] The polarizer may be prepared by forming a film from an aqueous polyvinyl alcohol solution, stretching the film uniaxially, and dyeing the film, or by dyeing the film, stretching the film uniaxially, and then performing a durability treatment, preferably with a boron compound. The film thickness of the polarizer is preferably within a range of 5 to 30 μm, and more preferably within a range of 5 to 15 μm.
[0226] As the polarizer, an ethylene-modified polyvinyl alcohol film having an ethylene unit content of 1 to 4 mol%, a polymerization degree of 2000 to 4000, and a saponification degree of 99.0 to 99.99 mol%, as described in JP-A-2003-248123 and JP-A-2003-342322, etc., is also preferably used. Among them, an ethylene-modified polyvinyl alcohol film having a hot water cutting temperature in the range of 66 to 73° C. is preferably used. A polarizer using this ethylene-modified polyvinyl alcohol film has excellent polarization performance and durability, and has little color spotting, and is particularly preferably used for large liquid crystal display devices.
[0227] It is also preferable to prepare a polarizing plate by preparing a coating type polarizer by the methods described in JP-A-2011-100161, JP-B-4691205, JP-B-4751481, and JP-B-4804589 and laminating the coating type polarizer with the laminate film of the present invention.
[0228] <Protective film> The protective film usable in the polarizing plate of the present invention can be obtained, for example, as a commercially available product. As the protective film, for example, a commercially available cellulose acylate film (for example, Konica Minolta TAC KC8UX, KC5UX, KC4UX, KC8UCR3, KC4SR, KC4BR, KC4CR, KC4DR, KC4FR, KC4KR, KC8UY, KC6UY, KC4UY, KC4UE, KC8UE, KC8UY-HA, KC2UA, KC4UA, KC6UA, KC2UAH, KC4UAH, KC6UAH, manufactured by Konica Minolta, Inc.) is preferably used.
[0229] The thickness of the protective film is not particularly limited, but can be about 10 to 100 μm, preferably in the range of 10 to 80 μm, more preferably in the range of 10 to 60 μm, and particularly preferably in the range of 10 to 40 μm.
[0230] The protective film may further have other layers, if necessary, in addition to the film body such as a cellulose acylate film, etc. Examples of the other layers include an antireflection layer, an antistatic layer, a retardation layer, and a brightness improving film layer.
[0231] <Adhesive layer> The adhesive layer may be a layer obtained by drying a completely saponified aqueous solution of polyvinyl alcohol (water paste), or may be a layer of a cured product of an active energy ray-curable adhesive.
[0232] <Method of manufacturing polarizing plate> The polarizing plate of the present invention can be produced by laminating the laminated film of the present invention and a polarizer. The method for laminating the laminated film of the present invention and the polarizer is not particularly limited, and can be performed by saponifying the laminated film and then using a fully saponified polyvinyl alcohol adhesive. The laminated film of the present invention and the polarizer can also be laminated by using an active energy ray curable adhesive or the like. Lamination using an active energy ray curable adhesive is preferred because the elastic modulus of the resulting adhesive layer is high, which makes it easy to suppress deformation of the polarizing plate and has high resistance to changes in the external environment (heat, humidity, etc.).
[0233] Known active energy ray-curable adhesives for polarizing plates include photoradical polymerization type compositions that utilize photoradical polymerization, photocationic polymerization type compositions that utilize photocationic polymerization, and hybrid type compositions that utilize both photoradical polymerization and photocationic polymerization.
[0234] Known examples of photoradical polymerization compositions include a composition containing a specific ratio of a radical polymerizable compound containing a polar group such as a hydroxy group or a carboxy group and a radical polymerizable compound not containing a polar group, as described in JP-A-2008-009329.
[0235] In particular, the radical polymerizable compound is preferably a compound having a radically polymerizable ethylenically unsaturated bond. Preferred examples of the compound having a radically polymerizable ethylenically unsaturated bond include compounds having a (meth)acryloyl group. Examples of the compound having a (meth)acryloyl group include N-substituted (meth)acrylamide compounds and (meth)acrylate compounds. "(meth)acryloyl" means one or both of acryloyl and methacryloyl. The same applies to (meth)acrylamide and (meth)acrylate.
[0236] Further, examples of the photocationic polymerization composition include active energy ray-curable adhesives containing the following components: (α) a cationic polymerizable compound, (β) a photocationic polymerization initiator, (γ) a photosensitizer that exhibits maximum absorption at wavelengths longer than 380 nm, and (δ) a naphthalene-based photosensitizer auxiliary, as disclosed in JP2011-028234A. However, other active energy ray-curable adhesives may also be used.
[0237] An example of a method for producing a polarizing plate using an active energy ray curable adhesive will be described below. A polarizing plate can be produced by a production method including: (1) a pretreatment step of subjecting a surface of a laminated film to which a polarizer is to be bonded for easy adhesion; (2) an adhesive application step of applying the above-mentioned active energy ray curable adhesive to at least one of the bonding surfaces between the polarizer and the laminated film; (3) a bonding step of bonding the polarizer and the optical film together via the obtained adhesive layer; and 4) a curing step of curing the adhesive layer in a state in which the polarizer and the optical film are bonded together via the adhesive layer. The pretreatment step (1) may be carried out as necessary.
[0238] (Pretreatment process) In the pretreatment step, an adhesion treatment is performed on the surface of the laminate film that is to be bonded to the polarizer, for example, the surface of the laminate film on the substrate side. When a laminate film and a protective film are bonded to both sides of the polarizer, respectively, an adhesion treatment is performed on the surface of the protective film that is to be bonded to the polarizer together with the laminate film. Examples of the adhesion treatment include corona discharge treatment and plasma treatment.
[0239] (Adhesive application process) In the adhesive application step, the active energy ray curable adhesive is applied to at least one of the adhesive surfaces between the polarizer and the laminated film. When the active energy ray curable adhesive is applied directly to the surface of the polarizer or the laminated film, the application method is not particularly limited. For example, various coating methods such as a doctor blade, a wire bar, a die coater, a comma coater, and a gravure coater can be used. In addition, a method of casting the active energy ray curable adhesive between the polarizer and the laminated film and then applying pressure with a roller or the like to uniformly spread it out can also be used. In addition, when the polarizing plate has a protective film, the active energy ray curable adhesive is applied in the same manner to at least one of the adhesive surfaces between the polarizer and the protective film.
[0240] (Lamination process) After the active energy ray curable adhesive is applied in this manner, the laminated film is subjected to a lamination process. In this lamination process, for example, when the active energy ray curable adhesive is applied to the surface of the polarizer in the previous application process, a laminated film is superimposed thereon. When the active energy ray curable adhesive is applied to the surface of the laminated film in the previous application process, a polarizer is superimposed thereon. When the active energy ray curable adhesive is cast between the polarizer and the laminated film, the polarizer and the laminated film are superimposed in this state.
[0241] In the case where a laminate film and a protective film are bonded to both sides of a polarizer and an active energy ray curable adhesive is used for both sides, the laminate film and the protective film are laminated on both sides of the polarizer via the active energy ray curable adhesive. In this state, the laminate film and the protective film are usually pressed by being sandwiched between rollers or the like from both sides (the polarizer side and the laminate film side when the laminate film is laminated on one side of the polarizer, and the laminate film and the protective film side on both sides when the laminate film and the protective film are laminated on both sides of the polarizer). The rollers can be made of metal, rubber, or the like. The rollers arranged on both sides may be made of the same material or different materials.
[0242] (hardening process) In the curing step, the uncured active energy ray curable adhesive is irradiated with active energy rays to cure the adhesive layer, forming an adhesive layer made of a cured product of the active energy ray curable adhesive. This allows the polarizer, laminate film, and optional protective film, which are superimposed via the active energy ray curable adhesive, to be bonded together. When the laminate film is attached to one side of the polarizer, the active energy rays may be irradiated from either the polarizer side or the laminate film side. In addition, when the laminate film and the protective film are attached to both sides of the polarizer, respectively, it is advantageous to irradiate the laminate film and the protective film to both sides of the polarizer with active energy rays from either one of the film sides in a state where the laminate film and the protective film are superimposed on both sides of the polarizer via the active energy ray curable adhesive, and simultaneously cure the active energy ray curable adhesives on both sides.
[0243] As the active energy ray, visible light, ultraviolet light, X-rays, electron beams, etc. can be used, and since they are easy to handle and have a sufficient curing speed, electron beams or ultraviolet light are generally preferably used.
[0244] The electron beam irradiation conditions can be any suitable conditions as long as the adhesive can be cured. For example, the acceleration voltage of the electron beam irradiation is preferably in the range of 5 to 300 kV, more preferably in the range of 10 to 250 kV. If the acceleration voltage is less than 5 kV, the electron beam may not reach the adhesive, resulting in insufficient curing, and if the acceleration voltage is more than 300 kV, the penetration power through the sample is too strong, causing the electron beam to bounce back and damaging the laminated film, protective film, and polarizer. The irradiation dose is preferably in the range of 5 to 100 kGy, more preferably in the range of 10 to 75 kGy. If the irradiation dose is less than 5 kGy, the adhesive may not be cured sufficiently, and if it exceeds 100 kGy, the laminated film, protective film, and polarizer may be damaged, causing a decrease in mechanical strength and yellowing, and the desired optical characteristics may not be obtained.
[0245] Any suitable conditions can be adopted for the ultraviolet irradiation conditions as long as the adhesive can be cured. The irradiation amount of ultraviolet light is 50 to 1500 mJ / cm2 in terms of the cumulative light amount. 2 It is preferable that the range is 100 to 500 mJ / cm 2 It is more preferable that the range is within the range of 100 to 200 mm.
[0246] In the polarizing plate thus obtained, the thickness of the adhesive layer is not particularly limited, but is usually within the range of 0.01 to 10 μm, and preferably within the range of 0.5 to 5 μm.
[0247] [Liquid crystal display device] The liquid crystal display device of the present invention is characterized by being equipped with the polarizing plate of the present invention. The liquid crystal display device of the present invention can ensure good visibility by being equipped with the polarizing plate of the present invention using the laminate film of the present invention.
[0248] The liquid crystal display device of the present invention has, for example, the configuration shown in Fig. 3 and Fig. 4. Fig. 3 is a plan view of one example of the liquid crystal display device of the present invention, and Fig. 4 is a cross-sectional view of the liquid crystal display device shown in Fig. 3 along line XX. The liquid crystal display device 100 shown in Fig. 3 and Fig. 4 has a liquid crystal panel 30, a first polarizing plate 20a arranged on a viewing side surface Sa of the liquid crystal panel 30, and a second polarizing plate 20b arranged on a backlight side surface Sb of the liquid crystal panel 30. The first polarizing plate 20a and the second polarizing plate 20b are polarizing plates of the present invention that include the laminate films 10a and 10b of the present invention, respectively.
[0249] In the liquid crystal display device of the present invention, for example, at least the first polarizer of the first polarizer 20a and the second polarizer 20b is preferably the polarizer of the present invention, and it is more preferable that both of them are polarizers of the present invention.
[0250] The liquid crystal panel 30 has two glass substrates G and a liquid crystal cell L disposed therebetween. The liquid crystal panel 30 can be preferably used in a Twisted Nematic (TN) mode, a Super Twisted Nematic (STN) mode, an In-Plane Switching (IPS) mode, an Optically Compensated Birefringence (OCB) mode, an Electrically Controlled Birefringence (ECB) mode, a Vertical Alignment (VA) mode (including Multi-domain Vertical Alignment (MVA) and Patterned Vertical Alignment (PVA)), a Hybrid Aligned Nematic (HAN) mode, or the like. In order to increase the contrast, the VA (MVA, PVA) mode or the IPS mode is preferable.
[0251] In TN mode liquid crystal panels, rod-shaped liquid crystal molecules are essentially aligned horizontally when no voltage is applied, and are further aligned with a twist angle of 60 to 120 degrees. TN mode liquid crystal panels are most commonly used as color TFT liquid crystal display devices, and are described in many publications.
[0252] In a VA mode liquid crystal panel, rod-shaped liquid crystal molecules are aligned substantially vertically when no voltage is applied.
[0253] VA mode liquid crystal panels include (1) narrowly defined VA mode liquid crystal panels in which rod-shaped liquid crystal molecules are aligned substantially vertically when no voltage is applied and substantially horizontally when voltage is applied (described in JP-A-2-176625), (2) multi-domain VA mode liquid crystal panels (described in SID97, Digest of Tech. Papers (Proceedings) 28 (1997) 845) in order to widen the viewing angle, (3) n-ASM mode liquid crystal panels in which rod-shaped liquid crystal molecules are aligned substantially vertically when no voltage is applied and substantially horizontally when voltage is applied (described in Proceedings of the Japan Liquid Crystal Symposium 58-59 (1998)), and (4) SURVIVAIVAL mode liquid crystal panels (announced at LCD International 98).
[0254] An OCB mode liquid crystal panel is a bend alignment mode liquid crystal panel in which rod-shaped liquid crystal molecules are aligned in substantially opposite directions (symmetrically) at the top and bottom of the liquid crystal panel, and is disclosed in U.S. Pat. Nos. 4,583,825 and 5,410,422. Because the rod-shaped liquid crystal molecules are aligned symmetrically at the top and bottom of the liquid crystal panel, a bend alignment mode liquid crystal panel has a self-optical compensation function. Therefore, this liquid crystal mode is called an OCB (Optically Compensatory Bend) liquid crystal mode. An advantage of a bend alignment mode liquid crystal display device is its fast response speed.
[0255] An IPS mode liquid crystal panel is a type in which a lateral electric field is applied to a nematic liquid crystal to perform switching, and is described in detail in Proc. IDRC (Asia Display 1995), pp. 577-580 and pp. 707-710.
[0256] In an ECB mode liquid crystal panel, rod-shaped liquid crystal molecules are aligned substantially horizontally when no voltage is applied. The ECB mode is one of the liquid crystal display modes having the simplest structure, and is described in detail in, for example, JP-A-5-203946.
[0257] The first polarizing plate 20a has, in this order from above, a first laminate film 10a, a first polarizer 11a, and a first protective film 12a on the viewing side surface Sa of the liquid crystal panel 30. The first laminate film 10a has a base material 1 and an optical functional layer 2, and the optical functional layer 2 is attached to the viewing side surface Sa of the liquid crystal panel 30.
[0258] The second polarizing plate 20b has, in this order from the top, a second laminate film 10b, a second polarizer 11b, and a second protective film 12b on the backlight side surface Sb of the liquid crystal panel 30. The second laminate film 10b has a base material 1 and an optical functional layer 2, and the optical functional layer 2 is attached to the backlight side surface Sb of the liquid crystal panel 30.
[0259] It is preferable that the absorption axis of the first polarizer 11a and the absorption axis of the second polarizer 11b are perpendicular to each other (in a crossed Nicol state).
[0260] The liquid crystal panel 30 of the liquid crystal display device 100 has two glass substrates G and a liquid crystal cell L disposed therebetween. The liquid crystal cell L has, for example, a pair of alignment films between a pair of transparent electrodes, a liquid crystal layer between the alignment films, and further has a color filter on the inner side of the glass substrate G on the viewing side.
[0261] The thickness of the glass substrate G is preferably in the range of 0.3 to 0.7 mm, more preferably in the range of 0.3 to 0.5 mm. The polarizing plate of the present invention is small in dimensional change due to temperature and humidity, and is therefore preferably used for thin glass used in small and medium-sized mobile electronic devices.
[0262] In the liquid crystal display device 100, the surface of the optical functional layer 2 of the first laminate film 10a and the surface 2a of the liquid crystal panel 30 on the viewing side, and the surface of the optical functional layer 2 of the second laminate film 10b and the surface 2b of the liquid crystal panel 30 on the backlight side can be bonded by a known method. In some cases, they may be bonded via an adhesive layer (not shown). As the adhesive layer, an adhesive layer obtained from an active energy ray-curable adhesive similar to that used in the production of the polarizing plate described above is preferable.
[0263] The liquid crystal display device of the present invention is preferably an IPS mode type, since the effects of the present invention are more remarkable. A liquid crystal display device using the polarizing plate of the present invention is a liquid crystal display device having excellent viewing angle characteristics and excellent visibility with suppressed color unevenness, etc., due to the action of the laminate film of the present invention. EXAMPLES
[0264] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. In the examples, the terms "parts" and "%" are used, but they represent "parts by mass" or "% by mass" unless otherwise specified.
[0265] [Making laminated films] (1) Preparation of substrate (1-1) Synthesis of Cellulose Acylate Three types of cellulose acylates 1 to 3 having the types of acyl groups, the degrees of acyl group substitution, and the number average molecular weight (Mn) shown in Table II were synthesized according to the method described in JP-A-10-45804. Note that cellulose acylates 1 and 2 correspond to cellulose acylate (A), and cellulose acylate 3 is outside the scope of cellulose acylate (A).
[0266] [Table 2]
[0267] (1-2) Synthesis of sugar esters Sugar esters 1 to 5, in which the hydrogen atoms of the hydroxyl groups of the sugars shown in Table III were replaced with the acyl groups shown in Table III in the ratios shown in Table III, were synthesized according to the above synthesis example (esterification reaction of sucrose with benzoic anhydride). Specifically, sugar esters 1, 2, and 5 were prepared by changing benzoic anhydride to acetic anhydride in the above synthesis example, performing the esterification reaction, and adjusting the esterification rate in the same manner as above. Sugar ester 3 was prepared according to the above synthesis example. Sugar ester 4 was prepared by changing sucrose to glucose and benzoic anhydride to acetic anhydride in the above synthesis example, performing the esterification reaction, and adjusting the esterification rate in the same manner as above.
[0268] Sugar esters 1 to 4 are sugar esters that correspond to sugar ester (B), and sugar ester 5 is a sugar ester outside the scope of sugar ester (B).
[0269] [Table 3]
[0270] (1-3) Preparation of substrate The substrate for the laminated film was prepared by a solution casting method as follows.
[0271] (Preparation of dope) Dopes 1 to 9 having the compositions shown in Table IV were prepared. Specifically, first, methylene chloride and ethanol, which are solvents, were added to a pressurized dissolution tank. Cellulose acylate, sugar ester, and matting agent were added to the pressurized dissolution tank containing the solvent while stirring, and the mixture was heated and stirred to be completely dissolved and dispersed. The matting agent shown in Table IV was all a 12% ethanol dispersion of Aerosil R812 (manufactured by Nippon Aerosil Co., Ltd.).
[0272] The obtained liquid was filtered using Azumi Filter Paper No. 244 manufactured by Azumi Filter Paper Co., Ltd. to obtain dopes 1 to 9.
[0273] [Table 4]
[0274] (Preparation of substrate 1) The dope 1 prepared above was uniformly cast on a stainless steel band support at 22°C and 1.8m wide using a belt casting apparatus. The solvent was evaporated at 40°C for 1 minute on the stainless steel band support, and then at 60°C until the residual solvent amount became 20%, and the web 1 was peeled off from the stainless steel band support at a peeling tension of 162N / m.
[0275] Next, the solvent was evaporated from the peeled web 1 at 35°C, and the web was slit to a width of 1.6 m. Then, using a tenter stretching machine, the web was stretched 1.05 times the original width in the width direction (TD direction) at a temperature of (Tg+20)°C, where Tg is the glass transition temperature of the substrate 1 (Tg measured using a substrate sample previously prepared using the material constituting the substrate 1 as described above). At this time, the amount of residual solvent when stretching using the tenter stretching machine was started was 4% by mass. Then, the web was transported through a drying zone at 120°C and 140°C with multiple rollers to finish drying, and the substrate 1 was produced. The thickness of the substrate was 40 μm.
[0276] (Preparation of Substrates 2 to 9) Substrates 2 to 9, each having a thickness of 40 μm, were prepared in the same manner as above, except that dope 1 was changed to dopes 2 to 9.
[0277] (Preparation of substrate 10) The dope 1 prepared above was uniformly cast on a stainless steel band support at 22°C and 1.8m wide using a belt casting apparatus. The solvent was evaporated at 65°C for 1 minute and then at 40°C until the residual solvent amount was 20%, and the web 10 was peeled off from the stainless steel band support at a peeling tension of 162N / m. The web 10 was then stretched and dried in the same manner as the web 1 was stretched and dried in the preparation of the substrate 1, to prepare a substrate 10 having a thickness of 40µm.
[0278] <Optical properties of substrate> For the obtained substrates 1 to 10, the value T (slope T of the out-of-plane retardation) was calculated based on the above formula (1) from the out-of-plane retardation R650 measured with light having a wavelength of 650 nm and the out-of-plane retardation R450 measured with light having a wavelength of 450 nm. The results are shown in Table V together with the composition of the materials contained in each substrate. In the table, the amount of sugar ester added is the amount added relative to 100 parts by mass of cellulose acylate.
[0279] [Table 5]
[0280] (2) Synthesis of materials for optical functional layers As materials for the optical functional layer, fumaric acid ester polymers 1 to 3 were produced.
[0281] <Synthesis Example 1> In a 30-liter autoclave, 18 kg of distilled water containing 0.2% by mass of partially saponified polyvinyl alcohol, 3 kg of diisopropyl fumarate, and 7 g of dimethyl-2,2'-azobisisobutyrate as a polymerization initiator were charged, and suspension radical polymerization reaction was carried out under the conditions of a polymerization temperature of 50°C and a polymerization time of 24 hours. The obtained particles were filtered, thoroughly washed with methanol, and dried at 80°C to obtain a diisopropyl fumarate homopolymer. The number average molecular weight of the obtained diisopropyl fumarate homopolymer was 160,000. The diisopropyl fumarate homopolymer is a fumarate ester polymer in which 100% of the ester moiety is isopropyl ester. The diisopropyl fumarate homopolymer was designated as fumarate ester polymer 1.
[0282] <Synthesis Example 2> In a 1-liter reactor equipped with a stirrer, a cooling tube, a nitrogen inlet tube, and a thermometer, 600 g of distilled water, 3.4 g of hydroxypropyl methylcellulose (manufactured by Shin-Etsu Chemical Co., Ltd., trade name Metolose 60SH-50) as a dispersant, 350.9 g of diisopropyl fumarate, 49.1 g of diethyl fumarate (14.0 parts by mass relative to 100 parts by mass of diisopropyl fumarate), and 8.3 g of t-butyl peroxypivalate as an oil-soluble radical initiator were placed, and after nitrogen bubbling for 1 hour, the mixture was stirred at 400 rpm and held at 50°C for 28 hours to carry out radical suspension polymerization. After the polymerization reaction was completed, the contents were recovered from the reactor, the polymerized product was filtered, washed twice with distilled water and twice with methanol, and then dried under reduced pressure at 80°C (yield: 75%).
[0283] The number average molecular weight of the resulting fumaric acid ester copolymer was 138,000. 1 H-NMR measurement confirmed that the obtained fumarate copolymer was a diisopropyl fumarate-diethyl fumarate copolymer with diisopropyl fumarate polymerized units / diethyl fumarate polymerized units=87 / 13 (mol%). In other words, the obtained fumarate copolymer was a fumarate copolymer in which 87% of the ester moieties were isopropyl ester. This fumarate copolymer was named fumarate polymer 2.
[0284] <Synthesis Example 3> Polymerization was carried out in the same manner as in Synthesis Example 2 above, except that the molar ratio of diisopropyl fumarate and diethyl fumarate used in the polymerization was changed to 7:3 (diisopropyl fumarate:diethyl fumarate), to obtain a diisopropyl fumarate-diethyl fumarate copolymer having a number average molecular weight of 140,000 and diisopropyl fumarate polymerized units / diethyl fumarate polymerized units=70 / 30 (mol %). In other words, the obtained fumarate ester copolymer is a fumarate ester copolymer in which 70% of the ester moieties are isopropyl ester. This fumarate ester copolymer is designated as fumarate ester polymer 3.
[0285] (3) Preparation of laminated film Using the substrates 1 to 10 and the fumaric acid ester polymers 1 to 3 prepared above, laminated films were prepared as follows.
[0286] (Preparation of Laminated Film 1) The fumaric acid ester polymer 1 obtained in Synthesis Example 1 was dissolved in a solution of toluene:methyl ethyl ketone in a mass ratio of 1:1 to prepare a 10% solution. The obtained coating solution was applied onto a substrate 1 by a doctor blade method so that the thickness of the layer after drying would be 2 μm, and then dried to form an optical functional layer, and a laminated film 1 was obtained.
[0287] (Preparation of Laminated Films 2 to 16) Laminated films 2 to 16 were produced in the same manner as above for producing laminated film 1, except that the type of substrate, the type of fumaric acid ester polymer, and the thickness of the optical functional layer were changed as shown in Table VI.
[0288] [Evaluation of laminated film] The optical properties and interlayer adhesion of the obtained laminated films 1 to 16 were evaluated as follows. The results are shown in Table VI together with the types of substrates and optical functional layers used in the preparation. In the table, "isopropyl %" indicates the percentage of isopropyl ester in the ester portion of the fumaric acid ester polymer.
[0289] (1) Optical properties The ratio Rth450 / Rth550 between the out-of-plane retardation Rth450 measured with light having a wavelength of 450 nm and the out-of-plane retardation Rth550 measured with light having a wavelength of 550 nm was calculated. Rth450 / Rth550 and Rth550 are shown in the table.
[0290] (2) Adhesion An NT cutter was used to make 11 cuts in each direction at 1 mm intervals on the optical functional layer of the laminated film, forming 100 squares. A cellophane adhesive tape (Cellotape (registered trademark) No. 405, 24 mm wide, manufactured by Nichiban Co., Ltd.) was applied on top of the film, and a peeling test was performed in which the tape was quickly pulled in the vertical (90°) direction. The adhesion was evaluated according to the number of peeled squares, according to the following evaluation criteria. The test was performed in an environment of 23°C and 55% RH.
[0291] (Evaluation Criteria) ◎: 100 squares remaining 〇: The remaining number is between 90 and 99. ×: 89 or less squares remaining
[0292] [Table 6]
[0293] [Preparation of polarizing plate] A polarizing plate having a polarizer, a laminate film on one side of the polarizer, and a protective film on the other side was produced using the laminate films 1 to 16. The polarizer, the laminate film, and the protective film were bonded together using an active energy ray-curable adhesive.
[0294] (Preparation of polarizer) A 75 μm thick polyvinyl alcohol film with an average degree of polymerization of 2400 and a degree of saponification of 99.9 mol% was immersed in warm water at 30° C. for 60 seconds to swell. The obtained film was then immersed in an aqueous solution of 0.3% iodine / potassium iodide (mass ratio=0.5 / 8) and dyed while being stretched to 3.5 times. The obtained film was then stretched in an aqueous solution of boric acid ester at 65° C. to a total stretch ratio of 6 times. The obtained film was then dried in an oven at 40° C. for 3 minutes to obtain a polarizer with a thickness of 25 μm.
[0295] (Protective film) As a protective film, KC2UA (product name, cellulose acylate film, manufactured by Konica Minolta, Inc.) was prepared.
[0296] (Adhesive 1: Photo-radical polymerization type active energy ray curing adhesive) 50 parts by mass of HEAA (hydroxyethyl acrylamide, manufactured by Kojin Co., Ltd.), 50 parts by mass of HEA (2-hydroxyethyl acrylate, manufactured by Kojin Co., Ltd.), and 3 parts by mass of IRGACURE819 manufactured by BASF Japan Ltd. as a photoradical polymerization initiator were mixed and stirred at 50°C for 1 hour to obtain adhesive 1.
[0297] (Preparation of Polarizing Plate 1) A corona discharge treatment was applied to the substrate side surface of the laminated film 1 and one surface of the protective film (KC2UA). The corona discharge treatment conditions were a corona output intensity of 2.0 kW and a line speed of 18 m / min. Next, the adhesive 1 prepared as described above was applied to the corona discharge treated surfaces of the laminated film 1 and the protective film using a bar coater so that the thickness of the adhesive layer after curing was 0.5 μm.
[0298] The adhesive-coated surfaces of the laminate film 1 and protective film were attached to both sides of the polarizer prepared as described above to obtain a laminate film 1 / coating layer of adhesive 1 / polarizer / coating layer of adhesive 1 / protective film (KC2UA). A belt conveyor-equipped ultraviolet irradiation device (the lamp used was a D bulb manufactured by Fusion UV Systems) was used to irradiate both sides of this laminate with an integrated light amount of 750 mJ / cm. 2 The coating layer of adhesive 1 was cured by irradiating it with ultraviolet light so as to obtain a polarizing plate 1 as an adhesive layer.
[0299] (Preparation of polarizing plates 2 to 16) Polarizing plates 2 to 16 were produced in the same manner as polarizing plate 1, except that laminate films 2 to 16 were used instead of laminate film 1.
[0300] [Fabrication of liquid crystal display device] A liquid crystal display device was produced using the polarizing plates 1 to 16 produced above. Specifically, Hitachi IPS mode liquid crystal television Wooo W32-L7000 was prepared. The schematic cross section of the liquid crystal television was configured as shown in FIG. 4, and in the liquid crystal television, both the polarizing plates on the viewing side and the backlight side that had been attached to the glass substrate surface of the liquid crystal panel were peeled off. Two polarizing plates 1 produced as described above were prepared, and the optical functional layer surface of the laminated film of each polarizing plate 1 was attached to the glass substrate surface of the viewing side and the backlight side of the liquid crystal panel, respectively, to produce a liquid crystal display device 1. In addition, when attaching, the absorption axis of the two polarizing plates 1 was attached so that it was in the same direction as the absorption axis of the two polarizing plates attached to the liquid crystal television used, on the viewing side and the backlight side, respectively, to produce a liquid crystal display device 1. Liquid crystal display devices 2 to 16 were produced in the same manner as above using polarizing plates 2 to 16.
[0301] [evaluation] The liquid crystal display devices 1 to 16 thus obtained were powered on, and a white image was displayed. The color unevenness and the difference in color between the left and right sides were evaluated as follows to evaluate the visibility from an oblique angle. The results are shown in Table VII.
[0302] (1) Uneven color The white image on the screen was visually observed from 45° to the right and 45° to the left facing the viewing side of the liquid crystal display device to confirm the color tone. The left and right sides were each evaluated according to the following criteria.
[0303] (Evaluation Criteria) ◎: No unevenness is visible at all. Good: Slight unevenness is visible, but visibility is not affected. ×: Unevenness is observed and visibility is poor.
[0304] (2) Left-right color difference The white image screen was visually observed from 45° to the right and 45° to the left facing the viewing side of the liquid crystal display device, and the difference in color between the left and right sides when checking the color was evaluated according to the following criteria.
[0305] (Evaluation Criteria) ◎: No difference in color between left and right. ○: There is a slight difference in color between the left and right sides, but it doesn't bother me. ×: There is a difference in color (for example, it appears blue when viewed from 45 degrees to the right, and red when viewed from 45 degrees to the left).
[0306] [Table 7]
[0307] It is evident from Tables VI and VII that the laminate film of the present invention has good interlayer adhesion, and that a liquid crystal display device using a polarizing plate having the laminate film can ensure good visibility. [Industrial Applicability]
[0308] According to the present invention, it is possible to provide a laminate film having a fumaric acid ester-based resin layer, which has good interlayer adhesion and can ensure good visibility in a liquid crystal display device using the laminate film, and a polarizing plate using the laminate film. In addition, it is possible to provide a liquid crystal display device that can ensure good visibility by using the laminate film. [Explanation of symbols]
[0309] 10, 10a, 10b Laminated film 1 Base material 2 Optical functional layer 20, 20a, 20b polarizing plate 11, 11a, 11b polarizer 12, 12a, 12b Protective film 100 LCD display device 30 Liquid crystal panel G Glass plate L Liquid crystal cell
Claims
1. A laminated film including a substrate and an optical functional layer, the substrate comprises a cellulose acylate having an acyl group substitution degree in the range of 2.6 to 3.0, and a sugar ester in which hydrogen atoms in 70 to 100% of hydroxy groups are substituted with acyl groups, The value T calculated based on the out-of-plane retardation R650 measured with light having a wavelength of 650 nm and the out-of-plane retardation R450 measured with light having a wavelength of 450 nm based on the following formula (1) is within a range of 0.040 to 0.055, Formula (1) T=(R650-R450) / (650-450) the optical functional layer contains a polymer containing fumaric acid ester polymerization units in a proportion of 90 mol % or more based on the total polymerization units, and 80 to 100% of the ester moieties of the fumaric acid ester polymerization units are isopropyl ester; A laminate film, wherein the ratio Rth450 / Rth550 of the out-of-plane retardation Rth450 measured with light having a wavelength of 450 nm to the out-of-plane retardation Rth550 measured with light having a wavelength of 550 nm is within the range of 1.2 to 1.
9.
2. 2. The laminate film according to claim 1, wherein the laminate film has an out-of-plane retardation Rth550 measured with light having a wavelength of 550 nm in the range of −30 to −15 nm.
3. A polarizing plate comprising the laminate film according to claim 1 or 2 laminated with a polarizer.
4. A liquid crystal display comprising the polarizing plate according to claim 3.
Citation Information
Patent Citations
Method of protecting face of slope
JP1977045109A
Method for producing cellulose ester film, cellulose ester film, polarizing plate, and liquid crystal display device
JP2006257380A
Optical film, its production method, and optical compensation film, polarizing plate, and liquid crystal display device using the same
JP2007051210A
Optical film
JP2008112141A
Optical compensation film
JP2009037110A